Polymer electrolytes, electrode active material binders, and secondary batteries

JP7933647B2Active Publication Date: 2026-10-13CANON KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022188750
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2026-10-13
Estimated Expiration
2042-11-25

AI Technical Summary

Benefits of technology

【0008】 本開示の少なくとも一つの態様によれば、高温環境下でも優れた強度を維持することができ、かつ、高いイオン導電性を有するポリマー電解質を得ることができる。また、本開示の少なくとも一つの態様によれば、高温環境下でも優れた強度を維持することができ、かつ、高いイオン導電性を有する電極活物質バインダーを得ることができる。さらに、本開示の少なくとも一つの態様によれば、優れたレート特性を示し、かつ、優れた耐衝撃性を有する二次電池を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933647000064
    Figure 0007933647000064
  • Figure 0007933647000065
    Figure 0007933647000065
  • Figure 0007933647000066
    Figure 0007933647000066
Patent Text Reader

Abstract

To provide a polymer electrolyte that has high ion conductivity and does not weaken in strength even in high-temperature environments.SOLUTION: This polymer electrolyte contains polyurethane, a lithium salt, and anions. The polyurethane has a three-dimensional crosslinking structure and has a cationic structure within the molecule.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to polymer electrolytes, electrode active material binders, and secondary batteries. [Background technology]

[0002] Lithium-ion rechargeable batteries are widely used as batteries for portable devices because they can extract significantly more electricity per unit volume and weight compared to other rechargeable batteries. A lithium-ion rechargeable battery consists of a positive electrode, a negative electrode, and an electrolyte. Currently, mainly organic electrolytes are used in lithium-ion rechargeable batteries, but the organic solvents used in these electrolytes are often flammable. Therefore, solid electrolytes are attracting attention from the perspective of safety concerns in the event of electrolyte leakage. Oxide-based, sulfide-based, and polymer-based materials are being widely investigated as solid electrolytes. Among these, oxide-based and sulfide-based solid electrolytes have relatively high ionic conductivity, but it is difficult to create a large interface with the active material in the electrode. Therefore, it has been proposed to use polymer electrolytes made of urethane resin, which have superior mechanical properties and can easily form a larger interface with the active material, compared to oxide-based and sulfide-based solid electrolytes.

[0003] Patent Document 1 describes a polyurethane resin with a number-average molecular weight of 1,000 to 500,000 obtained by reacting a polyetherdiol with an organic diisocyanate as essential components, and a polymer electrolyte using a lithium salt. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2016-69388 [Overview of the project] [Problems that the invention aims to solve]

[0005] In recent years, lithium-ion secondary batteries have been required to have not only high safety but also superior charge-discharge characteristics. According to the inventors' studies, the polyurethane contained in the polymer electrolyte composition described in Patent Document 1 tends to soften at high temperatures and its strength decreases. In secondary batteries using such a polymer electrolyte, for example as a bulk electrolyte, it is conceivable that a short circuit may occur when an impact is applied, for example, due to the decrease in the strength of the polyurethane in a high-temperature environment. Therefore, the inventors investigated introducing a three-dimensional crosslinking structure to the polyurethane in the polymer electrolyte in order to suppress the decrease in strength under high-temperature conditions and to more reliably prevent short circuits when impact is applied under high-temperature conditions. In the process, they found that polymer electrolytes containing polyurethane with a three-dimensional crosslinking structure may experience a decrease in ionic conductivity. At least one aspect of this disclosure aims to provide a polymer electrolyte that can maintain excellent strength even in high-temperature environments and has high ionic conductivity. At least one aspect of this disclosure aims to provide an electrode active material binder that can maintain excellent strength even in high-temperature environments and has high ionic conductivity. Furthermore, at least one aspect of this disclosure aims to provide a secondary battery that exhibits excellent rate characteristics and has excellent shock resistance. [Means for solving the problem]

[0006] According to at least one aspect of this disclosure, A polymer electrolyte, The polymer electrolyte contains polyurethane, a lithium salt, and an anion. The polyurethane is provided as a polymer electrolyte having a three-dimensional crosslinked structure and a cation structure within the molecule.

[0007] Furthermore, according to at least one aspect of this disclosure, an electrode active material binder containing the polymer electrolyte of this disclosure is provided. Furthermore, according to at least one aspect of the present disclosure, a secondary battery is provided comprising a positive electrode, a negative electrode, and a bulk electrolyte disposed between the positive electrode and the negative electrode, wherein at least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte is the polymer electrolyte described above. [Effects of the Invention]

[0008] According to at least one aspect of this disclosure, a polymer electrolyte can be obtained that maintains excellent strength even in high-temperature environments and has high ionic conductivity. Furthermore, according to at least one aspect of this disclosure, an electrode active material binder can be obtained that maintains excellent strength even in high-temperature environments and has high ionic conductivity. Moreover, according to at least one aspect of this disclosure, a secondary battery can be obtained that exhibits excellent rate characteristics and has excellent shock resistance. [Brief explanation of the drawing]

[0009] [Figure 1] A schematic cross-sectional view of a secondary battery using the polymer electrolyte of this disclosure as a bulk electrolyte. [Figure 2] A schematic cross-sectional view of a secondary battery using the polymer electrolyte of this disclosure as a binder for the positive electrode active material. [Figure 3] A schematic cross-sectional view of a secondary battery using the polymer electrolyte of this disclosure as a binder for the positive electrode active material, a bulk electrolyte, and a binder for the negative electrode active material. [Modes for carrying out the invention]

[0010] In this disclosure, unless otherwise specified, the expressions "XX or greater and YY or less" or "XX to YY" that represent a numerical range mean a numerical range that includes the lower and upper limits. Furthermore, when a numerical range is described in steps, the upper and lower limits of each numerical range can be combined in any way.

[0011] Figures 1 to 3 show examples of secondary batteries using the polymer electrolyte of this disclosure. The secondary battery 1 shown in Figure 1 represents an example of the schematic configuration of an all-solid-state secondary battery using a polymer electrolyte according to one embodiment of this disclosure as a bulk electrolyte 7, which will be described later. Here, the bulk electrolyte refers to a solid electrolyte that is placed between the positive electrode and the negative electrode as a lithium-ion mobile phase in a secondary battery and also functions as a separator. In the secondary battery 1 shown in Figure 1, a positive electrode active material 3 is provided on a positive electrode current collector 2 and fixed by a binder 4 for the positive electrode active material, forming a positive electrode 6. The positive electrode 6 may also contain a conductive additive 5.

[0012] The negative electrode active material 8, provided on the negative electrode current collector 9, forms the negative electrode 10. In Figure 1, the negative electrode active material layer represents metallic lithium, indium, etc. A layer of bulk electrolyte 7 is provided between the positive electrode 6 and the negative electrode 10.

[0013] The secondary battery 1 shown in Figure 2 represents an example of a schematic configuration of a secondary battery in which a polymer electrolyte is used as a binder 4 for the positive electrode active material. In the embodiment of Figure 2, the positive electrode 6 contains a polymer electrolyte. For example, the positive electrode 6 contains a positive electrode active material 3 and a binder 4 for the positive electrode active material that fixes the positive electrode active material. The binder 4 of the positive electrode active material is the polymer electrolyte of this disclosure. In the configuration of Figure 2, the bulk electrolyte 7 represents an oxide-based or sulfide-based inorganic solid electrolyte. The other configurations are the same as in Figure 1.

[0014] Figure 3 shows a secondary battery 1, which represents an example of a schematic configuration of a secondary battery in which a polymer electrolyte is used as a binder 4 for the positive electrode active material, a bulk electrolyte 7, and a binder 11 for the negative electrode active material. In the configuration of Figure 3, the positive electrode, bulk electrolyte, and negative electrode all contain a polymer electrolyte. Specifically, the positive electrode 6 has a positive electrode active material 3 and a binder 4 for the positive electrode active material that fixes the positive electrode active material, and the binder 4 for the positive electrode active material is the polymer electrolyte of this disclosure. The bulk electrolyte 7 is also the polymer electrolyte of this disclosure. The negative electrode 10 has a negative electrode active material 8 and a binder 11 for the negative electrode active material that fixes the negative electrode active material 8, and the binder 11 for the negative electrode active material is the polymer electrolyte of this disclosure. In the configuration of Figure 3, the negative electrode active material 8 represents a carbon material such as graphite. The other configurations are the same as in Figure 1.

[0015] In order to more effectively achieve the effects of this disclosure, it is preferable that the bulk electrolyte 7 is a polymer electrolyte according to one aspect of this disclosure, as shown in Figures 1 and 3, and penetrates the positive electrode active material 3 and the negative electrode active material 8 to increase the contact area.

[0016] (Method for manufacturing solid-state rechargeable batteries) Solid-state rechargeable batteries can be manufactured using known cell manufacturing methods such as laminate cell type, coin cell type, and pressurized cell type. The laminate cell type will be explained below as an example.

[0017] A laminate is obtained in which a positive electrode, a bulk electrolyte, and a negative electrode are arranged between a positive electrode current collector and a negative electrode current collector. Electrode tabs are welded to the positive electrode and the negative electrode current collector. The laminate, in which the positive electrode current collector, the positive electrode, the bulk electrolyte, the negative electrode, and the negative electrode current collector are laminated in this order, is wrapped with an aluminum laminate film, and sealed while reducing pressure with a vacuum packaging machine. The end portions of the electrode tabs are exposed outside the laminate film, and the electrode tabs and the aluminum laminate film are sealed in a state where they are bonded together by thermocompression bonding. After sealing, if necessary, pressurization may be performed using an isostatic pressurization device or the like. Examples of the bulk electrolyte include solid electrolytes and polymer electrolytes, and both may be used for lamination. In addition to the above laminate, other layers such as an elastic material and a resin material may be laminated inside the aluminum laminate film for the purpose of strength, molding, and the like. Moreover, a bipolar type in which a plurality of the laminates are stacked may be adopted.

[0018] (Positive Electrode Current Collector) The positive electrode current collector holds the positive electrode active material and supplies current to the positive electrode active material. Examples of the positive electrode current collector include metal foils and the like. Examples of the metal include aluminum, stainless steel, copper, silver, gold, platinum, nickel, and palladium. The metals may be used singly or in combination of two or more kinds.

[0019] (Positive Electrode Active Material) The positive electrode active material is a substance used for the positive electrode as an active material of a battery. The positive electrode active material is not particularly limited, and for example, positive electrode active materials used in secondary batteries such as lithium ion secondary batteries can be used. For example, (CF) m , (C2F) m , MnO2, TiS2, MoS2, FeS2, Li xa CoO2, Li xa NiO2, Li xa MnO2, Li xa Co y Ni 1-y O2, Li xa Co y M 1-y O z , Li xa Ni 1-y M y O z , Li xbMn2O4, Li xb Mn 2-y M y Examples include O4 (wherein M in each of the above formulas represents at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B; xa = 0 to 1.2, xb = 0 to 2.0, y = 0 to 0.9, and z = 2.0 to 2.3), vanadium oxide and its lithium compounds, niobium oxide and its lithium compounds, conjugated polymers using organic conductive materials, and olivine compounds. Note that the xa and xb values ​​in each of the above compositional formulas are the values ​​before the start of charging and discharging, and will increase or decrease during charging and discharging. The positive electrode active material can be used individually or in combination of two or more types.

[0020] (Conductive additive) The conductive additive is not particularly limited as long as it has the desired electronic conductivity. Examples include graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black, conductive fibers such as carbon fibers and metal fibers, metal powders such as aluminum powder, conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene derivatives. The conductive additive can be used alone or in combination of two or more types.

[0021] (Active material binder) The active material binder is not particularly limited as long as it is chemically and electrically stable. Examples include polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl polyacrylate, polyethyl polyacrylate, polyhexyl polyacrylate, polymethacrylic acid, polymethyl polymethacrylate, polyethyl polymethacrylate, polyhexyl polymethacrylate, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene-butadiene rubber, and carboxymethylcellulose.

[0022] A polymer electrolyte according to one aspect of this disclosure may be used as a bulk electrolyte, as an electrode active material binder such as a binder for a positive electrode active material and a binder for a negative electrode active material, or as a bulk electrolyte, a binder for a positive electrode active material, and a binder for a negative electrode active material. In other words, it is preferable that the secondary battery satisfies at least one of the following conditions (i) to (iii). (i) The positive electrode 6 comprises a positive electrode active material 3 and a binder 4 for the positive electrode active material that fixes the positive electrode active material, wherein the binder 4 for the positive electrode active material contains the polymer electrolyte of the present disclosure. (ii) The bulk electrolyte 7 comprises the polymer electrolyte of the present disclosure. (iii) The negative electrode 10 comprises a negative electrode active material 8 and a binder 11 for the negative electrode active material that fixes the negative electrode active material 8, wherein the binder 11 for the negative electrode active material comprises the polymer electrolyte of the present disclosure.

[0023] When the polymer electrolyte of this disclosure is used as a binder for the positive electrode active material or the negative electrode active material, it is particularly preferable because it provides good wettability to the active material surface of the positive or negative electrode and reduces interfacial resistance. The active material binder may be used alone or in combination of two or more types.

[0024] The positive electrode 6 can be produced, for example, by pressing a positive electrode mixture onto the surface of the positive electrode current collector 2, or applying a positive electrode mixture slurry thereto, drying the same, and rolling the same as necessary to form the positive electrode 6. The positive electrode mixture can be prepared, for example, by kneading a positive electrode active material, a conductive agent, and a binder for the positive electrode active material. The positive electrode mixture slurry can be prepared, for example, by dissolving or dispersing the positive electrode active material, the conductive agent, and the binder for the positive electrode active material in a liquid medium such as dehydrated N-methyl-2-pyrrolidone and ethylene glycol ethers.

[0025] (Negative Electrode Current Collector) The negative electrode current collector holds the negative electrode active material and supplies current to the negative electrode active material. Examples of the negative electrode current collector include metal foils and the like. Examples of the metal include aluminum, stainless steel, copper, silver, gold, platinum, nickel, and palladium. The metals may be used singly or in a combination of two or more may be used in combination.

[0026] (Negative Electrode Active Material) Examples of the negative electrode active material include metals, metal fibers, carbon materials, oxides, nitrides, silicon, silicon compounds, tin, tin compounds, various alloy materials, and the like. Above all, from the viewpoint of capacity density, metals, oxides, carbon materials, silicon, silicon compounds, tin, tin compounds and the like are preferred. Examples of the metal include metal Li and In-Li, and examples of the oxide include Li4Ti5O 12 (LTO: Lithium Titanate) and the like. Examples of the carbon material include various natural graphites, coke, non-graphitized carbon, carbon fibers, spherical carbon, various artificial graphites, amorphous carbon and the like. Examples of the silicon compound include silicon-containing alloys, silicon-containing inorganic compounds, silicon-containing organic compounds, solid solutions and the like. Examples of the tin compound include SnO b (0<b<2), SnO2, SnSiO3, Ni2Sn4, Mg2Sn and the like. Furthermore, the above-mentioned negative electrode material may contain a conductive additive. Examples of conductive additives include graphite such as natural graphite and artificial graphite, and carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black. When a polymer electrolyte is used as a bulk electrolyte, graphite can be particularly preferably used as the negative electrode active material.

[0027] Examples of conductive additives include conductive fibers such as carbon fibers, carbon nanotubes, and metal fibers; metal powders such as carbon fluoride and aluminum; conductive whiskers such as zinc oxide; conductive metal oxides such as titanium oxide; and organic conductive materials such as phenylene dielectrics.

[0028] (solid electrolyte) Solid electrolytes can be used in secondary batteries as bulk electrolytes sandwiched between two electrodes (positive and negative electrodes). They can also be used as additives to enhance the conductivity of lithium ions by being incorporated into the active material layer of at least one electrode selected from the group consisting of positive and negative electrodes. The polymer electrolyte of this disclosure can be suitably used as either a bulk electrolyte or an additive. This allows for a larger contact interface between the bulk electrolyte and the positive and negative electrode active materials, and furthermore, it has the flexibility to follow the expansion and contraction of the positive and negative electrode active materials, thereby improving the characteristics of the secondary battery.

[0029] For the bulk electrolyte and auxiliary agents, solid electrolytes other than polymer electrolytes according to one aspect of this disclosure may be used. Examples of solid electrolytes other than polymer electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, and complex hydride-based solid electrolytes. Oxide-based solid electrolytes include Li 1.5 Al 0.5 Ge 1.5 (PO4)3 and Li 1.3 Al 0.3 Ti 1.7 Nasicone-type compounds such as (PO4)3, Li 6.25 La3Zr2Al0.25 O 12 Examples of garnet-type compounds include Li 0.33 Li 0.55 Examples include perovskite-type compounds such as TiO3. Also, oxide-based solid electrolytes include Li 14 Examples include lithicone-type compounds such as Zn(GeO4)4, and acidic compounds such as Li3PO4, Li4SiO4, and Li3BO3. Specific examples of sulfide-based solid electrolytes include Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5. Furthermore, the solid electrolyte may be crystalline or amorphous, and may be glass ceramic. Note that descriptions such as Li2S-P2S5 refer to sulfide-based solid electrolytes made using raw materials containing Li2S and P2S5.

[0030] The polymer electrolytes of this disclosure include bulk electrolytes, binders for positive electrode active materials, and negative electrode active materials. It can be used as an electrode active material binder, such as a binder for [a specific type of material]. Below, the structure of a polymer electrolyte according to one embodiment of this disclosure will be described in detail.

[0031] The polymer electrolyte of this disclosure is preferably a solid electrolyte, such as a dry polymer electrolyte or a gel electrolyte. More preferably, it is a dry polymer electrolyte. The polymer electrolyte is preferably substantially free of liquid components, such as a liquid electrolyte. The liquid component content in the dry polymer electrolyte is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less.

[0032] (Polymer electrolyte) A polymer electrolyte according to one embodiment of the present disclosure contains polyurethane, a lithium salt, and an anion. The polyurethane has a three-dimensional crosslinked structure. By including polyurethane having a three-dimensional crosslinked structure in the polymer electrolyte, the decrease in strength under high-temperature conditions can be suppressed. On the other hand, the inventors speculate as follows as to why the polymer electrolyte exhibits the unexpected effect of high ionic conductivity despite containing polyurethane having a three-dimensional crosslinked structure to suppress the decrease in strength under high-temperature conditions.

[0033] Lithium salts, which are supporting electrolytes, have high polarity. On the other hand, polyurethanes obtained by reacting isocyanates and polyols usually have very few parts that dissociate into cations and anions. Therefore, they generally have lower polarity compared to liquid electrolytes such as ionic liquids. Consequently, when a polymer electrolyte containing polyurethane also contains lithium salts, the high polarity of the lithium salts causes them to aggregate and precipitate. As a result, the amount of lithium salt that the polymer electrolyte can dissolve tends to be small. Furthermore, using polyurethane with a three-dimensional crosslinked structure to suppress the decrease in strength under high-temperature conditions can easily hinder lithium ion movement due to steric hindrance caused by the crosslinked structure. As a result, polymer electrolytes containing polyurethane with a three-dimensional crosslinked structure and lithium salts tend to have low ionic conductivity.

[0034] A polymer electrolyte according to one aspect of this disclosure contains polyurethane, a lithium salt, and an anion. The polyurethane has a three-dimensional crosslinked structure. Furthermore, the polyurethane has a cationic structure within its molecule. Therefore, the polymer electrolyte has a highly polar structure. When the polymer electrolyte has a highly polar structure, the polarity difference between the polyurethane and the lithium salt, which is the supporting electrolyte, becomes smaller, making it less likely for the lithium salt to precipitate. As a result, the lithium salt content of the polymer electrolyte can be increased. On the other hand, the anions paired with the cation structure within the polyurethane molecule also interact with the lithium cation, thus hindering ion movement. Therefore, it was expected that this would lower ionic conductivity. However, an unexpected effect of improved ionic conductivity was observed. This is thought to be due to the interaction of the cation structure with the lithium salt anions within the polyurethane molecule, improving the dissociation rate of the lithium salt. This improvement in dissociation rate likely outweighed the effect of the anions in the polyurethane in suppressing lithium cation movement, resulting in improved ionic conductivity.

[0035] (Polyurethane) Polyurethane has a three-dimensional crosslinked structure, and also has a cation structure within its molecule. The method for obtaining such polyurethane is not particularly limited, but it can be obtained by reacting an ionic compound having a functional group that can react with an isocyanate group (e.g., a hydroxyl group) with an isocyanate compound such as polyisocyanate and a polyol. Alternatively, it can be obtained by reacting a urethane prepolymer, a polyol, and an ionic compound as described later. It can also be obtained by using the following method. In this case, at least one selected from the group consisting of polyols and isocyanate compounds is used that has three or more functional groups. That is, the polyol has at least three hydroxyl groups, or the isocyanate compound has at least three isocyanate groups. Specifically, for example, it is preferable to use a raw material mixture containing the following i), ii), or iii) as the raw material mixture for polyurethane. i) A combination of a polyol having at least three hydroxyl groups and an isocyanate compound having at least two isocyanate groups; ii) A combination of a polyol having at least two hydroxyl groups and an isocyanate compound having at least three isocyanate groups; iii) A combination of a polyol having at least three hydroxyl groups and an isocyanate compound having at least three isocyanate groups.

[0036] (Polyol) The polyol is not particularly limited, but a polyol having at least two hydroxyl groups is preferred. For example, at least one selected from the group consisting of polyether polyols, polyester polyols, polycaprolactone polyols, polycarbonate polyols, polyolefin polyols, and acrylic polyols is preferred. Among these, polyether polyols are preferred from the viewpoint of conductivity. Furthermore, when using an isocyanate compound having two isocyanate groups as the isocyanate compound described later, the polyol is preferably a polyol having at least three hydroxyl groups.

[0037] As the polyether polyol, at least one selected from the group consisting of diol and triol types of polyethylene glycol, diol and triol types of polypropylene glycol, poly-1,4-butanediol, poly-1,5-pentanediol, polyneopentyl glycol, poly-3-methyl-1,4-butanediol, poly-3-methyl-1,5-pentanediol, poly-1,6-hexanediol, poly-1,8-octanediol, poly-1,9-nonanediol, poly-1,4-butanediol-3-methyl-1,4-butanediol copolymer, and diol and triol types of polyethylene glycol-propylene glycol copolymer can be used.

[0038] When using a polyethylene glycol-propylene glycol copolymer as the polyol, the molar ratio of the polyethylene glycol structure to the polypropylene glycol structure is preferably 90:10 to 50:50, and particularly preferably 80:20 to 90:10. When the molar ratio of the ethylene glycol structure to the propylene glycol structure is within this range, the lithium ion transportability by polyethylene glycol can be maintained at a high level, and inhibition of lithium ion movement due to polymer crystallization can be easily suppressed.

[0039] Furthermore, the number-average molecular weight of the polyol is preferably 1,000 to 10,000, and particularly preferably 3,000 to 5,000. If the number-average molecular weight is less than 1,000, although the mechanical strength is excellent, the crosslinking conversion distance becomes shorter, resulting in a higher crosslinking density and a tendency for ion mobility to decrease. On the other hand, if the number-average molecular weight is 10,000 or more, there are fewer crosslinking sites, and the crosslinking density becomes too low, which tends to reduce mechanical strength. If the number-average molecular weight is in the range of 1,000 to 10,000, it is easier to ensure mechanical strength while maintaining ion mobility. Furthermore, if the number-average molecular weight is in the range of 3,000 to 5,000, crystallization at low temperatures due to interactions between polyols is less likely to occur, and ion mobility at low temperatures is improved, making it even more preferable.

[0040] The degree of development of crosslink density in polyurethane is determined by the methyl ethyl ketone immersion method of polymer electrolytes. This can be confirmed by the volume swelling rate. It is preferable that the volume swelling rate of the polymer electrolyte using methyl ethyl ketone (MEK) is 30.0 to 100.0%. It is preferable that the volume swelling rate of the polymer electrolyte be within the above range because it allows for a high level of balance between the ionic conductivity of the polymer electrolyte and the mechanical strength in high-temperature environments. For example, if it is 100.0% or less, it is less likely to cause a decrease in mechanical strength in high-temperature environments due to a low crosslinking density. Also, if the volume swelling rate is 30.0% or more, it is less likely to cause an ion movement inhibition effect due to a high crosslinking density. The volume swelling rate of the polymer electrolyte is more preferably 30.0 to 80.0%, and even more preferably 40.0 to 80.0%.

[0041] The volume swelling rate is the ratio of the volume of polyurethane before and after saturation by a specific solvent. The volume swelling rate is calculated using the following formula, but the volume of the test specimen is calculated from its weight in air and its weight in water. Specific measurement methods will be described later. Volume swelling rate (%) = (Volume when saturated by swelling after solvent immersion) / (Volume before solvent immersion) × 100

[0042] (Isocyanate compounds) The isocyanate compound is not particularly limited, but isocyanate compounds having at least two isocyanate groups are preferred. For example, aliphatic polyisocyanates such as ethylene diisocyanate and 1,6-hexamethylene diisocyanate (HDI); alicyclic polyisocyanates such as isophorone diisocyanate (IPDI), cyclohexane 1,3-diisocyanate, and cyclohexane 1,4-diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate (TDI), 1,4-phenylene diisocyanate, 4,4-diphenylmethane diisocyanate (MDI), polymeric diphenylmethane diisocyanate (polymeric MDI), xylylene diisocyanate, and naphthalene diisocyanate, as well as copolymers, isocyanurates, TMP adducts, biuret compounds, and block compounds thereof can be used. These isocyanate compounds can be used alone or in combination of two or more types. Among these, it is preferable to include at least one selected from the group consisting of 1,4-phenylenediisocyanate, 4,4-diphenylmethane diisocyanate, and polymeric MDI, and more preferably to include at least one selected from the group consisting of polymeric MDI and 1,4-phenylenediisocyanate. When using a polyol having two hydroxyl groups (i.e., a diol type) as described above, the isocyanate compound is preferably an isocyanate compound having at least three isocyanate groups, such as polymeric MDI.

[0043] Among the above, polymeric MDI is preferred. Here, polymeric MDI is a mixture of monomeric MDI and high molecular weight polyisocyanate, and is represented by the following formula (A). In formula (A), n is preferably between 0 and 4. Polymeric MDI can be commercially available, such as the Millionate MR series (manufactured by Tosoh Corporation), including the Millionate MR200 (product name). [ka]

[0044] Furthermore, a urethane prepolymer obtained by reacting a polyol, such as the polyether polyol mentioned above, with the isocyanate compound mentioned above may be used as the isocyanate compound. The urethane prepolymer represents a polymer obtained by reacting a polyol with a polyisocyanate. The urethane prepolymer has at least one isocyanate group and has a polyether structure. When the urethane prepolymer is an isocyanate compound, the content of the isocyanate compound used in the synthesis of the urethane prepolymer is preferably 1.0 to 200.0 parts by mass, more preferably 5.0 to 100.0 parts by mass, even more preferably 10.0 to 50.0 parts by mass, particularly preferably 10.0 to 40.0 parts by mass, and especially preferably 10.0 to 30.0 parts by mass, per 100 parts by mass of polyol. Furthermore, when the urethane prepolymer is an isocyanate compound, the isocyanate content in the urethane prepolymer is preferably 1.0 to 5.0% by mass, and more preferably 1.5 to 3.5% by mass. Having the isocyanate content within this range makes it easier to control the crosslinking density.

[0045] The content of the isocyanate compound is not particularly limited, but is preferably 50.0 to 480.0 parts by mass, more preferably 60.0 to 400.0 parts by mass, even more preferably 70.0 to 300.0 parts by mass, particularly preferably 70.0 to 200.0 parts by mass, and especially preferably 70.0 to 150.0 parts by mass per 100 parts by mass of polyol.

[0046] (Cation structure) Polyurethanes have a cationic structure within their molecules. Preferably, the anion contained in this cationic structure and the polymer electrolyte is a residue formed by the reaction of an ionic compound containing a cationic structure with a reactive functional group capable of reacting with an anion and an isocyanate group, with an isocyanate group. An ionic compound comprising a cationic structure having a reactive functional group that can react with an anion and an isocyanate group comprises an anion and a cationic structure having at least one functional group (e.g., a hydroxyl group) that can react with an isocyanate group. Examples of functional groups that can react with an isocyanate group include a hydroxyl group and an amino group, with a hydroxyl group being preferred. The content of the ionic compound is preferably 0.5 to 5.0 parts by mass, more preferably 0.7 to 3.0 parts by mass, and even more preferably 1.0 to 2.0 parts by mass, per 100 parts by mass of the total of the polyol and isocyanate. When the content of the ionic compound is within this range, it is possible to achieve a high level of both improved compatibility of the lithium salt, which is the supporting electrolyte, and improved dissociation rate. The cation structure and anion of ionic compounds are described below. Note that the combination of cation structure and anion is not particularly limited.

[0047] The cation structure preferably includes at least one selected from the group consisting of a cationic nitrogen-containing heterocyclic structure and ammonium cations having a linear or branched structure. This can increase the polarity of the polyurethane. The cationic nitrogen-containing heterocyclic structure is not particularly limited, but may be a four-membered to eight-membered ring. Cationic nitrogen-containing heterocyclic structures include cationic nitrogen-containing aromatic heterocyclic structures such as imidazolium cation, pyridinium cation, pyrazinium cation, pyrimidinium cation, azepinium cation, quinolinium cation, isoquinolinium cation, indolinium cation, quinoxalinium cation, triazolium cation, triazinium cation, and thiazolinium cation; pyrrolidinium cation, pyrrolidinium cation, imidazolinium cation, imidazolidinium cation, piperadinium cation, azepanium cation, 1,3-diazepanium cation, and 1,4-diazepanium cation. Examples of cationic nitrogen-containing aliphatic heterocyclic structures include diazepanium cations, azokanium cations, oxazolinium cations, and morpholinium cations. Among these, at least one selected from the group consisting of imidazolium cation, pyridinium cation, and pyrazinium cation is preferred as the cationic nitrogen-containing aromatic heterocyclic structure, with imidazolium cation being more preferred. At least one selected from the group consisting of pyrrolidinium cation and piperazinium cation is preferred as the cationic nitrogen-containing aliphatic heterocyclic structure, with pyrrolidinium cation being more preferred.

[0048] Examples of ammonium cations having a linear or branched structure include primary ammonium cations, secondary ammonium cations, tertiary ammonium cations, and quaternary ammonium cations, with quaternary ammonium cations being preferred among them. The hydrocarbon group of the ammonium cation is not particularly limited, but may have, for example, a hydrocarbon group having 1 to 8 carbon atoms (preferably 1 to 4, more preferably 1 to 2, and even more preferably 1). Furthermore, the ammonium cation having a linear or branched structure may have the structure shown in formula (4) below.

[0049] The cation structure may have any substituents, such as hydrocarbon groups. For example, it is preferable that the cation structure includes at least one structure selected from the group consisting of structures represented by the following formulas (1) to (6). The following describes each of the structures represented by formulas (1) to (6).

[0050] The structure shown in equation (1) will be explained below. [ka] In formula (1), d 1 R represents an integer between 0 and 3 (preferably 0 or 1). 1 and R 2 This represents a hydrocarbon group that forms a five-membered ring nitrogen-containing aromatic heterocyclic structure together with a nitrogen atom. 1 ~Z 2 Each of these independently represents the structure shown by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) with a hydroxyl group. Also, Z 3 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) with a hydroxyl group. Furthermore, Z 1 , Z 2 , and d 1 When is 1 or more, at least one Z 3 At least one selected from the group consisting of , is a structure represented by the following formula (X).

[0051] As the hydrocarbon group having 1 to 4 carbon atoms, alkyl groups having 1 to 4 carbon atoms are preferred, alkyl groups having 1 to 2 carbon atoms are more preferred, and alkyl groups having 1 carbon atom are even more preferred. The hydrocarbon group having hydroxyl groups and having 1 to 4 carbon atoms is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. It may also have two or more hydroxyl groups. The structure represented by formula (1) represents a five-membered ring nitrogen-containing aromatic heterocyclic cation having at least one structure represented by the following formula (X) and two nitrogen atoms. Furthermore, the nitrogen-containing aromatic heterocyclic structure in formula (1) is preferably, for example, an imidazolium cation. The method for incorporating the structure shown in formula (1) into the polyurethane molecule is not particularly limited. However, for example, by reacting an ionic compound with a structure corresponding to the cation of the five-membered ring nitrogen-containing aromatic heterocyclic structure shown in formula (1) with an isocyanate compound, at least one structure shown in formula (1) is contained within the polyurethane molecule.

[0052] As the nitrogen-containing aromatic heterocyclic structure of the five-membered ring in formula (1), the cationic nitrogen-containing aromatic heterocyclic structure described in the section on cation structures above can be used, and among these, the imidazolium cation is preferred. An example of an ionic compound with a structure corresponding to the cation of the nitrogen-containing aromatic heterocyclic structure of the five-membered ring in formula (1) is Z in formula (1). 1 , Z 2 , and d 1 When is 1 or more, at least one Z 3 Examples of ionic compounds include those in which at least one selected from the group consisting of , has a hydroxyl group and is a divalent hydrocarbon having a straight or branched chain. By reacting such an ionic compound with an isocyanate compound, the structure shown in formula (1) can be obtained. Examples of such ionic compounds include ionic compounds containing an imidazolium cation, which are listed below.

[0053] 1-methyl-3-hydroxymethylimidazolium cation, 1-methyl-3-(2-hydroxyethyl)imidazolium cation, 1-methyl-3-(3-hydroxypropyl)imidazolium cation, 1-methyl-3-(4-hydroxybutyl)imidazolium cation, 1-ethyl-3-(2-hydroxyethyl)imidazolium cation, 1-n-butyl-3-(2-hydroxyethyl)imidazolium cation, 1,3-dimethyl-2-(2-hydroxyethyl)imidazolium cation, 1,3-dimethyl-2-(4-hydroxybutyl)imidazolium cation, 1,3-dimethyl-4-(2-hydroxyethyl)imidazolium cation; 1,3-bishydroxymethylimidazolium cation, 1,3-bis(2-hydroxyethyl)imidazolium cation, 2-methyl-1,3-bishydroxymethylimidazolium cation, 2-methyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 4-methyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 2-ethyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 4-ethyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 2-n-buty 1,3-bis(2-hydroxyethyl)imidazolium cation, 4-n-butyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 1,3-bis(3-hydroxypropyl)imidazolium cation, 1,3-bis(4-hydroxybutyl)imidazolium cation, 1-methyl-2,3-bis(2-hydroxyethyl)imidazolium cation, 1-methyl-3,4-bis(2-hydroxyethyl)imidazolium cation, 1-methyl-3,5-bis(2-hydroxyethyl)imidazolium cation; 1,2,3-Trishydroxymethylimidazolium cation, 1,2,3-Tris(2-hydroxyethyl)imidazolium cation, 1,2,3-Tris(3-hydroxypropyl)imidazolium cation, 1,2,3-Tris(4-hydroxybutyl)imidazolium cation, 1,3,4-Trishydroxymethylimidazolium cation, 1,3,4-Tris(2-hydroxyethyl)imidazolium cation, 1,3,4-Tris(3-hydroxypropyl)imidazolium cation, 1,3,4-Tris(4-hydroxybutyl)imidazolium cation; and derivatives thereof.

[0054] The structure shown in equation (2) will be explained below. [ka] In formula (2), d 2 R represents an integer between 0 and 5 (preferably between 0 and 3, more preferably 0 or 1). 3 This represents a hydrocarbon group that forms a nitrogen-containing aromatic heterocyclic structure with a nitrogen atom. 4 Z represents the structure shown by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) that has a hydroxyl group. 5 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) with a hydroxyl group. Furthermore, Z 4 , and d 2 When is 1 or more, at least one Z 5 At least one selected from the group consisting of , is a structure represented by the following formula (X).

[0055] As the hydrocarbon group having 1 to 4 carbon atoms, alkyl groups having 1 to 4 carbon atoms are preferred, alkyl groups having 1 to 2 carbon atoms are more preferred, and alkyl groups having 1 carbon atom are even more preferred. The hydrocarbon group having hydroxyl groups and having 1 to 4 carbon atoms is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. It may also have two or more hydroxyl groups. The structure represented by formula (2) represents a nitrogen-containing aromatic heterocyclic cation having at least one structure represented by the following formula (X). The nitrogen-containing aromatic heterocyclic structure in formula (2) may be a five-membered to eight-membered ring, and is preferably a five-membered or six-membered ring. The nitrogen-containing aromatic heterocyclic structure in formula (2) is preferably, for example, a pyridinium cation. The method for incorporating the structure shown in formula (2) into the polyurethane molecule is not particularly limited, but for example, by reacting an ionic compound with a structure corresponding to the cation of the nitrogen-containing aromatic heterocyclic structure shown in formula (2) with an isocyanate group, at least one structure shown in formula (2) is included in the polyurethane molecule.

[0056] As the nitrogen-containing aromatic heterocyclic structure in formula (2), the cationic nitrogen-containing aromatic heterocyclic structures described in the section on cation structures above can be used, with pyridinium cations being preferred. An example of an ionic compound with a structure corresponding to the cation of the nitrogen-containing aromatic heterocyclic structure in formula (2) is Z in formula (2). 4 , and d 2 When is 1 or more, at least one Z 5 Examples of ionic compounds include those in which at least one selected from the group consisting of , has a hydroxyl group and is a divalent hydrocarbon having a straight or branched chain. By reacting such an ionic compound with an isocyanate compound, the structure shown in formula (2) can be obtained. Examples of such ionic compounds include ionic compounds containing a pyridinium cation, which are listed below.

[0057] 1-Hydroxymethylpyridinium cation, 1-(2-hydroxyethyl)pyridinium cation, 1-(3-hydroxypropyl)pyridinium cation, 1-(4-hydroxybutyl)pyridinium cation, 2-methyl-1-(2-hydroxyethyl)pyridinium cation, 3-methyl-1-(2-hydroxyethyl)pyridinium cation, 4-methyl-1-(2-hydroxyethyl)pyridinium cation, 3-ethyl-1-(2-hydroxyethyl)pyridinium cation, 3-n-butyl-1-(2-hydroxyethyl)pyridinium cation, 1-methyl-2-hydroxymethylpyridinium catio n, 1-methyl-3-hydroxymethylpyridinium cation, 1-methyl-4-hydroxymethylpyridinium cation, 1-methyl-2-(2-hydroxyethyl)pyridinium cation, 1-methyl-3-(2-hydroxyethyl)pyridinium cation, 1-methyl-4-(2-hydroxyethyl)pyridinium cation, 1-ethyl-3-(2-hydroxyethyl)pyridinium cation, 1-n-butyl-3-(2-hydroxyethyl)pyridinium cation, 2-methyl-4-n-butyl-1-(2-hydroxyethyl)pyridinium cation; 1,2-Bishydroxymethylpyridinium cation, 1,3-Bishydroxymethylpyridinium cation, 1,4-Bishydroxymethylpyridinium cation, 1,2-Bis(2-hydroxyethyl)pyridinium cation, 1,3-Bis(2-hydroxyethyl)pyridinium cation, 1,4-Bis(2-hydroxyethyl)pyridinium cation, 1,2-Bis(3-hydroxypropyl)pyridinium cation, 1,2-Bis(3-hydroxypropyl)pyridinium cation, 1,3-Bis(3-hydroxypropyl)pyridinium cation, 1, 4-bis(3-hydroxypropyl)pyridinium cation, 1,2-bis(4-hydroxybutyl)pyridinium cation, 1,3-bis(4-hydroxybutyl)pyridinium cation, 1,4-bis(4-hydroxybutyl)pyridinium cation, 2-methyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 2-ethyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 5-methyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 5-ethyl-1,3-bis(2-hydroxyethyl)pyridinium cation; 1,2,4-Trishydroxymethylpyridinium cation, 1,2,4-Tris(2-hydroxyethyl)pyridinium cation, 1,2,4-Tris(3-hydroxypropyl)pyridinium cation, 1,2,4-Tris(4-hydroxybutyl)pyridinium cation, 1,3,5-Trishydroxymethylpyridinium cation, 1,3,5-Tris(2-hydroxyethyl)pyridinium cation, 1,3,5-Tris(3-hydroxypropyl)pyridinium cation, 1,3,5-Tris(4-hydroxybutyl)pyridinium cation; and derivatives thereof.

[0058] The structure shown in equation (3) will be explained below. [ka] In formula (3), d 3 R represents an integer between 0 and 4 (preferably between 0 and 2). 4 and R 5This represents a hydrocarbon group that forms a six-membered ring nitrogen-containing aromatic heterocyclic structure together with a nitrogen atom. Z 6 Z represents the structure shown by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) that has a hydroxyl group. 7 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) with a hydroxyl group. Furthermore, Z 6 , and d 3 When is 1 or more, at least one Z 7 At least one selected from the group consisting of , is a structure represented by the following formula (X).

[0059] As the hydrocarbon group having 1 to 4 carbon atoms, alkyl groups having 1 to 4 carbon atoms are preferred, alkyl groups having 1 to 2 carbon atoms are more preferred, and alkyl groups having 1 carbon atom are even more preferred. The hydrocarbon group having hydroxyl groups and having 1 to 4 carbon atoms is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. It may also have two or more hydroxyl groups. The structure represented by formula (3) represents a cation of a six-membered ring nitrogen-containing aromatic heterocyclic structure having at least one structure represented by the following formula (X) and two nitrogen atoms. Furthermore, the nitrogen-containing aromatic heterocyclic structure in formula (3) is preferably, for example, a pyrazinium cation. The method for incorporating the structure shown in formula (3) into the polyurethane molecule is not particularly limited, but for example, by reacting an ionic compound with a structure corresponding to the cation of the six-membered ring nitrogen-containing aromatic heterocyclic structure shown in formula (3) with an isocyanate compound, at least one structure shown in formula (3) can be contained within the polyurethane molecule.

[0060] As the nitrogen-containing aromatic heterocyclic structure of the six-membered ring in formula (3), the cationic nitrogen-containing aromatic heterocyclic structures described in the section on cation structures above can be used, with pyrimidinium cations and pyrazinium cations being preferred. An example of an ionic compound with a structure corresponding to the cation of the nitrogen-containing aromatic heterostructure of the six-membered ring in formula (3) is Z in formula (3). 6 , and d 3 When is 1 or more, at least one Z 7 Examples of ionic compounds include those in which at least one selected from the group consisting of , has a hydroxyl group and is a divalent hydrocarbon having a straight or branched chain. By reacting such an ionic compound with an isocyanate compound, the structure shown in formula (3) can be obtained. Examples of such ionic compounds include ionic compounds containing pyrimidium cations, which are listed below.

[0061] 1,4-bis(2-hydroxyethyl)pyrimidinium cation, 1,5-bis(3-hydroxybutyl)pyrimidinium cation, 1-(4-hydroxybutyl)-4-(2-hydroxyethyl)pyrimidinium cation, 1,4-bis(2-hydroxyethyl)-2-methylpyrimidinium cation; and derivatives thereof.

[0062] The structure shown in equation (4) will be explained below. [ka] In formula (4), R 7 represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2), Z 8 ~Z 10 Each of these independently represents the structure shown in the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) with a hydroxyl group, and Z 8 ~Z 10 At least one of the groups consisting of the following is a structure represented by the following formula (X).

[0063] As the hydrocarbon group having 1 to 4 carbon atoms, alkyl groups having 1 to 4 carbon atoms are preferred, alkyl groups having 1 to 2 carbon atoms are more preferred, and alkyl groups having 1 carbon atom are even more preferred. The hydrocarbon group having hydroxyl groups and having 1 to 4 carbon atoms is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. It may also have two or more hydroxyl groups. The structure shown in formula (4) represents an ammonium cation having at least one structure represented by the following formula (X). The method for incorporating the structure shown in formula (4) into the polyurethane molecule is not particularly limited. However, for example, by reacting an ionic compound having a structure corresponding to the ammonium cation shown in formula (4) with an isocyanate compound, at least one structure shown in formula (4) is contained within the polyurethane molecule.

[0064] As the ammonium cation in formula (4), a linear or branched ammonium cation as described in the section on cation structure above can be used, and among these, a quaternary ammonium cation is preferred. An example of an ionic compound with a structure corresponding to the ammonium cation in formula (4) is Z in formula (4). 8 ~Z 10 Examples of ionic compounds include those in which at least one selected from the group consists of a hydroxyl group and is a divalent hydrocarbon having a straight or branched chain. By reacting such an ionic compound with an isocyanate compound, the structure shown in formula (4) can be obtained. Examples of such ionic compounds include ionic compounds containing a quaternary ammonium cation, which are listed below.

[0065] 2-hydroxyethyltrimethylammonium cation, 2-hydroxyethyltriethylammonium cation, 4-hydroxybutyltrimethylammonium cation, 4-hydroxybutyl-tri-n-butylammonium cation; Bis(hydroxymethyl)dimethylammonium cation, bis(2-hydroxyethyl)dimethylammonium cation, bis(3-hydroxypropyl)dimethylammonium cation, bis(4-hydroxybutyl)dimethylammonium cation; Tris(hydroxymethyl)methylammonium cation, tris(2-hydroxyethyl)methylammonium cation, tris(3-hydroxypropyl)methylammonium cation, tris(4-hydroxybutyl)methylammonium cation; and derivatives thereof.

[0066] The structure shown in equation (5) will be explained below. [ka] In formula (5), d 4 R represents an integer between 0 and 4 (preferably between 0 and 3, more preferably between 0 and 2). 8 and R 9 This represents a hydrocarbon group that forms a nitrogen-containing aliphatic heterocyclic structure with a nitrogen atom. 11 ~Z 13 Each of these independently represents the structure shown by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) with a hydroxyl group. Also, Z 14 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) with a hydroxyl group. Furthermore, Z 11 ~Z 13 , and d 4 When is 1 or more, at least one Z 14 At least one selected from the group consisting of , is a structure represented by the following formula (X).

[0067] As the hydrocarbon group having 1 to 4 carbon atoms, alkyl groups having 1 to 4 carbon atoms are preferred, alkyl groups having 1 to 2 carbon atoms are more preferred, and alkyl groups having 1 carbon atom are even more preferred. The hydrocarbon group having 1 to 4 carbon atoms and a hydroxyl group is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. It may also have 2 or more hydroxyl groups. The structure represented by formula (5) represents a cation of a nitrogen-containing aliphatic heterocyclic structure that has at least one structure represented by the following formula (X) and two nitrogen atoms. In addition, the nitrogen-containing aliphatic heterocyclic structure in formula (5) may be a 5-membered ring to an 8-membered ring, and is preferably a 5-membered ring or a 6-membered ring. The nitrogen-containing aliphatic heterocyclic structure in formula (5) is preferably, for example, a piperazinium cation. The method for incorporating the structure represented by formula (5) into the polyurethane molecule is not particularly limited. For example, by reacting an ionic compound having a structure corresponding to the cation of the nitrogen-containing aliphatic heterocyclic structure represented by formula (5) with an isocyanate compound, at least one structure represented by formula (5) is contained in the polyurethane molecule.

[0068] As the nitrogen-containing aliphatic heterocyclic structure in formula (5), the cationic nitrogen-containing aliphatic heterocyclic structures described in the section of the above cation structure can be used, and among them, the piperazinium cation is preferred. Examples of the ionic compound having a structure corresponding to the cation of the nitrogen-containing aliphatic heterocyclic structure in formula (5) include Z in formula (5) 11 ~Z 13 , and d 4 is 1 or more, at least one Z 14 , at least one selected from the group consisting of is an ionic compound that is a divalent hydrocarbon having a hydroxyl group and a linear or branched structure. The structure represented by formula (5) can be obtained by reacting such an ionic compound with an isocyanate compound. As examples of such ionic compounds, ionic compounds containing a piperazinium cation are listed below.

[0069] 1,1-Bis(2-hydroxyethyl)piperazinium cation, 1,1,4-tris(2-hydroxyethyl)piperazinium cation, 1,4-bis(3-hydroxypropyl)-1-ethylpiperazinium cation, 1,4-bis(2-hydroxyethyl)-1,3-diethylpiperazinium cation; and derivatives thereof.

[0070] Hereinafter, the structure represented by formula (6) will be described.

Chemical Formula

[0071] As the hydrocarbon group having 1 to 4 carbon atoms, an alkyl group having 1 to 4 carbon atoms is preferred, an alkyl group having 1 to 2 carbon atoms is more preferred, and an alkyl group having 1 carbon atom is even more preferred. The hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. It may also have 2 or more hydroxyl groups. The structure represented by equation (6) has at least one structure represented by the following equation (X): This represents a cation with a nitrogen-containing aliphatic heterocyclic structure. The nitrogen-containing aliphatic heterocyclic structure in formula (6) may be a five-membered to eight-membered ring, and is preferably a five-membered or six-membered ring. The nitrogen-containing aliphatic heterocyclic structure in formula (6) is preferably, for example, a pyrrolidinium cation. The method for incorporating the structure shown in formula (6) into the polyurethane molecule is not particularly limited, but for example, by reacting an ionic compound with a structure corresponding to the cation of the nitrogen-containing aliphatic heterocyclic structure shown in formula (6) with an isocyanate group, at least one structure shown in formula (6) is included in the polyurethane molecule.

[0072] As the nitrogen-containing aliphatic heterocyclic structure in formula (6), the cationic nitrogen-containing aliphatic heterocyclic structures described in the section on cation structures above can be used, and among these, pyrrolidinium cations are preferred. An example of an ionic compound with a structure corresponding to the cation of the nitrogen-containing aliphatic heterocyclic structure in formula (6) is Z in formula (6). 15 , Z 16 , and d 5 When is 1 or more, at least one Z 17 Examples of ionic compounds include those in which at least one selected from the group consisting of , has a hydroxyl group and is a divalent hydrocarbon having a straight or branched chain. By reacting such an ionic compound with an isocyanate compound, the structure shown in formula (6) can be obtained. Examples of such ionic compounds include ionic compounds containing pyrrolidinium cations, which are listed below.

[0073] 1-methyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-ethyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-butyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-methyl-1,2-bis(4-hydroxybutyl)pyrrolidinium cation; and derivatives thereof.

[0074] The structure shown by equation (X) will be explained below. [ka] In formula (X), R 10 The symbol "*" represents a divalent hydrocarbon group having a straight or branched chain, the symbol "*" represents a bond with a nitrogen atom in formulas (1) to (6), or a bond with a carbon atom in a nitrogen-containing heterocyclic structure in formulas (1) to (3) and formulas (5) to (6), and the symbol "**" represents a bond with a carbon atom in a polymer chain constituting a polyurethane having a cationic structure. R 10 It is preferably a linear or branched alkylene group having 1 to 8 carbon atoms (preferably 1 to 4, more preferably 1 to 2). Also, R 10 It may have any substituent, such as a hydroxyl group.

[0075] The structure represented by formula (X) may be, for example, a structure formed by reacting an ionic compound with a structure corresponding to the cation of the structures represented by formulas (1) to (6) with an isocyanate compound. The isocyanate compound is preferably the urethane prepolymer described above.

[0076] Among the structures represented by formulas (1) to (6), when the cation structure includes the structure represented by formula (1) or formula (2), it exhibits high stability as a cation and a high dissociation rate with the counterion anion. Therefore, it is preferable because it readily interacts with the anion of the lithium salt contained as a supporting electrolyte, promoting the dissociation of the lithium salt and improving ionic conductivity.

[0077] Polyurethane has an ethylene oxide structure represented by the following formula (7) within its molecule. This is preferable. Having an ethylene oxide structure can increase the mobility of lithium ions in the polymer electrolyte. Furthermore, it is more preferable to have a propylene oxide structure represented by the following formula (8) in addition to the ethylene oxide structure. By having a propylene oxide structure in addition, the formation of crystal structures caused by the ethylene oxide structure can be suppressed. As a result, the mobility of lithium ions in the polymer electrolyte can be further increased. [ka] [ka]

[0078] A more preferred specific embodiment of the polyurethane is one in which at least an ethylene oxide structure represented by formula (7) is present between adjacent first urethane bonds and second urethane bonds. In particular, it is preferable that a propylene oxide structure represented by formula (8) is further present between the first urethane bond and the second urethane bond. In this case, the average number of moles added of the ethylene oxide structure represented by formula (7) is m 1 n is the average number of moles added to the propylene oxide structure shown in equation (8). 1 Therefore, m 1 and n 1 Each of these is an independent natural number greater than or equal to 1. Also, n 1 ≤m 1 ≤9n 1 It is preferable that the following conditions be met. 1 ≤m 1 ≤9n 1 By satisfying these conditions, crystallization of the polymer main chain is further suppressed, and the decrease in lithium ion mobility under low-temperature conditions can be further suppressed. m 1 The value is preferably 1 to 110, and more preferably 34 to 102. n 1 The value is preferably 1 to 55, and more preferably 5 to 43.

[0079] Furthermore, when multiple ethylene oxide structures and propylene oxide structures are included, each structure may be block copolymerized or random copolymerized. The method for producing such polyurethane is not particularly limited, but for example, it can be produced by using a polyethylene glycol-propylene glycol copolymer as the polyol and reacting it with an isocyanate compound. Alternatively, it can also be produced by reacting a urethane prepolymer, which is obtained by reacting a polyethylene glycol-propylene glycol copolymer with an isocyanate compound, with a polyol.

[0080] An example of the specific configuration described above is shown in equation (9) below. As shown in equation (9) below, adjacent to each other, 2 By having ethylene oxide and propylene oxide structures between the urethane bonds, crystallization of the polymer main chain is suppressed even when the molecular weight between crosslinking points is large, and the decrease in lithium ion mobility, especially in low-temperature environments, can be further suppressed. As a result, ionic conductivity and rate characteristics are more easily improved. [ka] In formula (9), L1 is a linking group having at least one ethylene oxide structure represented by formula (7), and preferably the linking group L1 further has at least one propylene oxide structure represented by formula (8).

[0081] When the linking group L1 has an ethylene oxide structure represented by formula (7) and a propylene oxide structure represented by formula (8), the average number of moles of the ethylene oxide structure represented by formula (7) is m. 1 , and the average number of added moles n of the propylene oxide structure represented by formula (8) above. 1 Each of these is an independent natural number greater than or equal to 1, and n 1 ≤m 1 ≤9n 1 It is preferable that this is the case.1 ≤m 1 ≤9n 1 By satisfying these conditions, crystallization of the polymer main chain is further suppressed, and the decrease in lithium ion mobility under low-temperature conditions can be further suppressed. m 1 The value is preferably 1 to 110, and more preferably 34 to 102. n 1 The value is preferably 1 to 55, and more preferably 5 to 43. The structure shown in formula (9) can be obtained, for example, by using a polyether polyol obtained by ring-opening polymerization of ethylene oxide and propylene oxide. Furthermore, when the linking group L1 contains multiple ethylene oxide structures and multiple propylene oxide structures, each structure may be block copolymerized or random copolymerized. In particular, it is preferable that the linking group L1 has a random copolymerized structure of ethylene oxide structures and propylene oxide structures. The linking group L1 may further contain a diol structure having 1 to 6 carbon atoms (preferably 4 to 6 carbon atoms) to the extent that it does not impair the effects of the present disclosure. For example, a diol structure may be included between the ethylene oxide structure and the propylene oxide structure. The diol structure is -OR x Represented by -O-, R x This is an alkylene group having 1 to 6 carbon atoms (preferably 4 to 6).

[0082] The structure of polyurethane can be confirmed by analyzing it using known methods such as pyrolysis GC / MS, TF-IR, and NMR.

[0083] (Anion structure) Examples of anions contained in polyurethane include fluoroalkylsulfonylimide anions, fluorosulfonylimide anions, fluoroalkyl sulfonate anions, fluorosulfonate anions, fluoroalkyl carboxylate anions, fluoroalkylmethide anions, fluoroborate anions, fluorophosphate anions, dicyanamide anions, thiocyanate anions, bisoxalatoborate anions, perchlorate anions, and derivatives thereof.

[0084] Examples of fluoroalkylsulfonylimide anions include fluoroalkylsulfonylimide anions having a fluoroalkyl group with 1 to 6 carbon atoms, such as bis(trifluoromethanesulfonyl)imide anion, bis(pentafluoroethanesulfonyl)imide anion, bis(heptafluoropropanesulfonyl)imide anion, bis(nonafluorobutanesulfonyl)imide anion, bis(dodecafluoropentanesulfonyl)imide anion, and bis(perfluorohexanesulfonyl)imide anion, as well as cyclic fluoroalkylsulfonylimide anions such as N,N-hexafluoropropane-1,3-disulfonylimide.

[0085] A specific example of a fluorosulfonylimid anion is the bis(fluorosulfonyl)imido anion. Examples of fluoroalkyl sulfonate anions include trifluoromethanesulfonate anion, fluoromethanesulfonate anion, perfluoroethanesulfonate anion, perfluoropropanesulfonate anion, perfluorobutanesulfonate anion, perfluoropentanesulfonate anion, perfluorohexanesulfonate anion, and perfluorooctanesulfonate anion. Examples of fluoroalkyl carboxylic acid anions include trifluoroacetate anion, perfluoropropionate anion, perfluorobutyrate anion, perfluorovalerate anion, and perfluorocaproate anion. Examples of fluoroalkylmethide anions include alkylsulfonyl fluoride methide anions such as tris(trifluoromethanesulfonyl)methide anion, tris(perfluoroethanesulfonyl)methide anion, tris(perfluoropropanesulfonyl)methide anion, tris(perfluorobutanesulfonyl)methide anion, tris(perfluoropentanesulfonyl)methide anion, tris(perfluorohexanesulfonyl)methide anion, and tris(perfluorooctanesulfonyl)methide anion.

[0086] Specific examples of fluoroborate anions include, for instance, the tetrafluoroborate anion. Specific examples of fluorophosphate anions include, for instance, the hexafluorophosphate anion.

[0087] Among these anions, at least one selected from the group consisting of fluoroalkylsulfonylimid anions, fluorosulfonylimid anions, fluoroborate anions, dicyanamide anions, and thiocyanate anions is particularly preferred because it exhibits less reduction in conductivity under low-temperature conditions.

[0088] (Lithium salt) The polymer electrolyte contains a lithium salt. The lithium salt is preferably included as a supporting electrolyte in lithium-ion secondary batteries. Examples of lithium salts include at least one selected from the group consisting of LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiAsF6, lithium lower aliphatic carboxylate, LiCl, LiBr, LiI, lithium chloroborane, lithium tetraphenylborate, LiN(CF3SO3)3, and LiN(C2F5SO2)2. Among these, at least one selected from the group consisting of LiN(CF3SO3)3, LiN(C2F5SO2)2, and LiClO4 is preferred. These lithium salts have high chemical stability with respect to lithium-based active materials, and insulating films are less likely to form at the negative electrode interface due to the decomposition of the lithium salt. Therefore, the resistance at the negative electrode interface is less likely to fluctuate. The lithium salts can be used individually or in combination of two or more.

[0089] The lithium salt content is preferably 0.8 to 40.0 parts by mass, more preferably 5.0 to 40.0 parts by mass, even more preferably 5.0 to 15.0 parts by mass, and particularly preferably 5.0 to 10.0 parts by mass, per 100 parts by mass of polyurethane in the polymer electrolyte. When the lithium salt content is within this range, it is well compatible with polyurethane, does not precipitate even at low temperatures, and high ionic conductivity can be obtained. The type and amount of lithium salt contained in the polymer electrolyte can be measured by LC-MS or similar methods after solvent extraction.

[0090] The polymer electrolyte may be, for example, a cured product of a mixture comprising at least one polyol, at least one isocyanate compound, an anion, an ionic compound having a functional group reactive with an isocyanate group and containing a cationic structure, and a lithium salt. Here, the mixture includes at least one selected from the group consisting of a polyol having at least three hydroxyl groups as the at least one polyol, and an isocyanate compound having at least three isocyanate groups as the at least one isocyanate compound. The mixture has at least three hydroxyl groups as the at least one polyol. By including at least one selected from the group consisting of a polyol and an isocyanate compound having at least three isocyanate groups as the at least one isocyanate compound, the cured product of the mixture will contain a polyurethane having a three-dimensional crosslinked structure. Specifically, it is preferable to use a raw material mixture containing, for example, the following i), ii), or iii) as the raw material mixture for polyurethane. i) A combination of a polyol having at least three hydroxyl groups and an isocyanate compound having at least two isocyanate groups; ii) A combination of a polyol having at least two hydroxyl groups and an isocyanate compound having at least three isocyanate groups; iii) A combination of a polyol having at least three hydroxyl groups and an isocyanate compound having at least three isocyanate groups.

[0091] The polyol is not particularly limited, and any of the above-mentioned polyols can be used. For example, a polyol with a molecular weight of 3000 to 5000 having an ethylene oxide structure represented by formula (7) and a propylene oxide structure represented by formula (8) can be used. The isocyanate compound is not particularly limited, and any of the above-mentioned isocyanate compounds can be used. For example, a urethane prepolymer can be used. As ionic compounds containing a cationic structure having a reactive functional group capable of reacting with anions and isocyanate groups, for example, ionic compounds with structures corresponding to the cationic structures shown in formulas (1) to (6) above can be used. As the lithium salt, the lithium salts mentioned above can be used. If necessary, the electrolyte solution may contain a known solvent. Examples of solvents include methyl ethyl ketone.

[0092] <Liquid electrolyte> The polymer electrolyte may include a liquid electrolyte, provided that it does not impair the effects of the present disclosure and does not compromise safety at high temperatures. Examples of liquid electrolytes include ionic liquids and non-aqueous electrolytes. Specific examples of ionic liquids include the following combinations of cations and anions. The cation is selected from the group consisting of quaternary ammonium, imidazolium, pyridinium, pyrrolidinium, and piperidinium, and is at least one of these. The anion may be at least one selected from the group consisting of fluoroalkylsulfonylimide anions, fluorosulfonylimide anions, fluoroalkyl sulfonate anions, fluorosulfonate anions, fluoroalkyl carboxylate anions, fluoroalkylmethide anions, fluoroborate anions, fluorophosphate anions, dicyanamide anions, thiocyanate anions, bisoxalatoborate anions, perchlorate anions, and derivatives thereof.

[0093] Non-aqueous electrolytes are liquids in which approximately 1 mole of lithium salt is dissolved in a non-aqueous solvent. Examples of non-aqueous solvents include ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Examples of lithium salts include LiPF6, LiBF4, and LiClO4.

[0094] While the inclusion of a liquid electrolyte may improve ionic conductivity, to avoid a decrease in mechanical strength at high temperatures, it is preferable that the liquid electrolyte be in amounts of, for example, 10 parts by mass or less, 5 parts by mass or less, 1 part by mass or less, or 0.5 parts by mass or less, relative to 100 parts by mass of polyurethane contained in the polymer electrolyte.

[0095] The polymer electrolyte may optionally contain nonconductive fillers such as silica, quartz powder, titanium dioxide, zinc oxide, and calcium carbonate. These nonconductive fillers, when added to the electrolyte-forming paint, function as film-forming aids when coating the paint during the electrolyte layer formation process. The content of such nonconductive fillers is preferably 0.1 to 10 parts by mass per 100 parts by mass of the resin forming the electrolyte layer.

[0096] Furthermore, the polymer electrolyte may, if necessary, contain a conductive filler, to the extent that it does not impair the effects of the present disclosure. Conductive fine particles such as carbon black, zinc oxide, tin oxide, and titanium oxide can be used as the conductive filler. In particular, when the polymer electrolyte is used as a binder for the positive or negative electrode active material, the inclusion of a conductive filler in the polymer electrolyte can reduce the internal resistance of the secondary battery. The content of the conductive filler is preferably 0.5 to 5 parts by mass per 100 parts by mass of polyurethane contained in the polymer electrolyte.

[0097] (Method for forming a polymer electrolyte layer) The method for forming the polymer electrolyte layer is not particularly limited. For example, the polymer electrolyte materials described above can be mixed by a known method to obtain an electrolyte solution for forming the polymer electrolyte layer. After applying the electrolyte solution by a known coating method such as bar coating, spin coating, or roll coating, the polymer material contained in the electrolyte solution can be polymerized by a known means such as UV to form the polymer electrolyte layer. The polymer electrolyte layer can be formed at a desired position, such as on the positive electrode or negative electrode. The thickness of the polymer electrolyte layer as the bulk electrolyte is preferably 5.0 μm or more and 100.0 μm or less. [Examples]

[0098] Specific examples and comparative examples relating to this disclosure are shown below. However, this disclosure is not limited to the examples and comparative examples described below.

[0099] <Synthesis of Polyols> (Polyether polyol A-1) 16.4 parts by mass of 1,4-butanediol (manufactured by Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of KOH (manufactured by Kojun Chemical Laboratory Co., Ltd.) were added to an autoclave and stirred under reduced pressure at 120°C until uniformly dissolved and dehydrated. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 983.6 parts by mass of alkylene oxide mixed in a mole fraction of EO:PO=9:1 was continuously introduced over 300 minutes while maintaining a gauge pressure of approximately 0.5 MPa. The reaction was allowed to proceed at the same temperature for 170 minutes until the pressure was below 0.2 MPa, and then the temperature was raised to 130°C over 20 minutes. The mixture was stirred for 150 minutes until the pressure change inside the autoclave was 0.01 MPa / 30 minutes to obtain a polyol. 18 parts by mass of water were added to the obtained polyol and stirred at 90°C for 30 minutes. Then, 50 g of alkali adsorbent (Kyoward 600, manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. The obtained liquid was filtered to remove the adsorbent. Subsequently, it was dried under reduced pressure at 130°C to obtain polyether polyol A-1 with a hydroxyl value of 22.5 mg KOH / g and a manganese content of 5,000.

[0100] (Polyether polyol A-2~A-5) Polyether polyols A-2 to A-5 were obtained in the same manner as polyether polyol A-1, except that the amount of 1,4-butanediol, the molar mixing ratio of EO:PO, and the amount of each component were changed as shown in Table 1. [Table 1] In the table, the alkylene oxide mixing ratio is expressed as mole fraction.

[0101] (Polyether polyol A-6) In a reaction vessel, a mixture of 216.3 parts by mass (3.0 mol) of dry tetrahydrofuran and 172.2 parts by mass (2.0 mol) of dry 3-methyltetrahydrofuran (molar mixing ratio 6 / 4) was maintained at a temperature of 15°C. 16.4 parts by mass of 70% perchloric acid and 120 parts by mass of acetic anhydride were added, and the reaction was carried out for 5 hours to obtain the reaction mixture. Next, the reaction mixture was poured into 600 parts by mass of 20% aqueous sodium hydroxide solution and purified. Further removal of residual water and solvent components under reduced pressure yielded polyether polyol A-6 with a hydroxyl value of 37.4 mgKOH / g and Mn 3,000.

[0102] (Polyether polyol A-7) Except for changing the reaction time to 2 hours, polyether polyol A-7 with a hydroxyl value of 93.5 mg KOH / g and Mn of 1,200 was obtained in the same manner as polyether polyol A-6.

[0103] (Polyether polyol A-8~A-15) Polyether polyols A-8 to A-15 are shown in Table 2 below. [Table 2] In the table, the EO / PO ratio indicates the alkylene oxide mixing ratio (mole fraction).

[0104] (Isocyanate-terminated prepolymer B-1) Under a nitrogen atmosphere, 100.0 parts by mass of polyether polyol A-1 was gradually added dropwise to 16.3 parts by mass of isocyanate C-1 polymeric MDI (trade name: Millionate MR-200, manufactured by Tosoh Corporation) in a reaction vessel, while maintaining the temperature in the reaction vessel at 65°C. After the addition was complete, the reaction was carried out at 65°C for 3.5 hours. The resulting reaction mixture was cooled to room temperature, and 49.8 parts by mass of methyl ethyl ketone was added to obtain a solution of isocyanate-terminated prepolymer B-1 with an isocyanate group content of 2.5% by mass.

[0105] (Isocyanate group-terminated prepolymers B-2 to B-15) Isocyanate-terminated prepolymers B-2 to B-15 were synthesized in the same manner as isocyanate-terminated prepolymer B-1, except that the types and amounts of isocyanate and polyol used in the reaction were changed as shown in Tables 3 and 4. [Table 3] [Table 4]

[0106] <Synthesis of ionic compounds> (Ionic compound I-01) A round-bottom flask fitted with a Liebig condenser is filled with a stirring bar and tetrahydrofuran (THF) 60 ml of (manufactured by Kanto Chemical Co., Ltd.) was added, and 24.0 g (0.60 mol) of sodium hydride (60% by mass, dispersed in liquid paraffin, manufactured by Tokyo Chemical Industry Co., Ltd.) was dispersed in it. The round-bottom flask was cooled in an ice bath. A solution of 10.2 g (0.15 mol) of imidazole (manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in 60 ml of THF was slowly added dropwise, and the ice bath was removed and the mixture was stirred at room temperature for 2 hours. 47.6 g (0.38 mol) of 2-bromoethanol (manufactured by Tokyo Chemical Industry Co., Ltd.) was added at room temperature, and the mixture was heated under reflux at 70°C for 7 hours. The reaction mixture was filtered, insoluble matter was washed away with THF, and the solvent of the resulting filtrate was removed by vacuum distillation. The obtained product was dissolved in 200 ml of dichloromethane, and an aqueous solution of 43.6 g (0.15 mol) of bis(trifluoromethanesulfonyl)imide lithium (manufactured by Tokyo Chemical Industry Co., Ltd.) was added as the anion starting material. The mixture was stirred at room temperature for 10 hours. The obtained solution was separated to obtain the organic layer. This organic layer was washed three times with pure water. Next, dichloromethane was removed by vacuum distillation to obtain ionic compound I-01. Ionic compound I-01 is a compound represented by the following formula. [ka]

[0107] (Ionic compounds I-02, 03) Ionic compounds I-02 and I-03 were obtained in the same manner as the synthesis of ionic compound I-01, except that the anionic raw materials and their proportions were changed as shown in Table 5. Ionic compounds I-02 and I-03 are compounds represented by the following formulas. [ka] [ka] [Table 5]

[0108] (Ionic compound I-04) A stirring bar and 50 ml of THF were placed in a round-bottom flask fitted with a Liebig condenser. 20.0 g of sodium hydride (60% by mass, dispersed in liquid paraffin, manufactured by Tokyo Chemical Industry Co., Ltd.) was dispersed in the flask, and the flask was cooled in an ice bath. A solution of 16.8 g (0.15 mol) of 1-(2-hydroxyethyl)imidazole (manufactured by Sigma-Aldrich) dissolved in 50 ml of THF was slowly added dropwise. After removing the ice bath, the flask was stirred at room temperature for 1 hour. 20.7 g (0.19 mol) of tan (manufactured by Tokyo Chemical Industry Co., Ltd.) was added at room temperature, and the mixture was heated under reflux at 80°C for 5 hours. The reaction solution was filtered, insoluble matter was washed away with THF, and the solvent of the resulting filtrate was removed by vacuum distillation. The obtained product was dissolved in 150 ml of dichloromethane, and an aqueous solution containing 43.6 g (0.15 mol) of bis(trifluoromethanesulfonyl)imide lithium (manufactured by Tokyo Chemical Industry Co., Ltd.) was added as the anionic starting material, and the mixture was stirred at room temperature for 10 hours. The resulting solution was separated to obtain the organic layer. This organic layer was washed three times with pure water. Next, the dichloromethane was removed by vacuum distillation to obtain ionic compound I-04. Ionic compound I-04 is a compound represented by the following formula. [ka]

[0109] (Ionic compound I-05) A stirring bar and 50 ml of acetonitrile were placed in a round-bottom flask fitted with a Liebig condenser. 22.7 g (0.15 mol) of 4-pyridinebutanol (Sigma-Aldrich) was added and dissolved. At room temperature, 29.1 g (0.19 mol) of 4-bromo-1-butanol (Tokyo Chemical Industries) was added dropwise over 30 minutes, and the mixture was heated under reflux at 90°C for 12 hours. Next, the reaction solution was cooled to room temperature, the acetonitrile was removed by distillation under reduced pressure, and the mixture was washed three times with 50 ml of diethyl ether. The obtained product was dissolved in 150 ml of dichloromethane, and an aqueous solution containing 35.1 g (0.16 mol) of potassium bis(fluorosulfonyl)imide was added as the anionic starting material. The mixture was stirred at room temperature for 12 hours. The resulting solution was separated to obtain the organic layer. This organic layer was washed three times with pure water. Next, the dichloromethane was removed by distillation under reduced pressure to obtain ionic compound I-05. Ionic compound I-05 is a compound represented by the following formula. [ka]

[0110] (Ionic compounds I-06, 07) Ionic compounds I-06 and I-07 were obtained in the same manner as the synthesis of ionic compound I-05, except that the anionic raw materials and their proportions were changed as shown in Table 6. Ionic compounds I-06 and I-07 are compounds represented by the following formulas. [ka] [ka] [Table 6]

[0111] (Ionic compound I-08) A stirring bar and 50 ml of THF were placed in a round-bottom flask fitted with a Liebig condenser. 20.0 g (0.50 mol) of sodium hydride (60% by mass, dispersed in liquid paraffin, manufactured by Tokyo Chemical Industry Co., Ltd.) was dispersed, and the flask was cooled in an ice bath. A solution of 25.2 g (0.15 mol) of 4-(2-ethyl-1H-imidazole-1-yl)butan-1-ol (manufactured by Aurorafine Chemical Co., Ltd.) dissolved in 60 ml of THF was slowly added dropwise. After removing the ice bath, the mixture was stirred at room temperature for 2 hours. 17.4 g (0.16 mol) of bromoethane was added dropwise over 30 minutes at room temperature, and the mixture was heated under reflux at 85°C for 12 hours. Next, 100 ml of pure water was added to the reaction solution, and the solvent was removed under reduced pressure. The resulting product was removed by Celite filtration, and the solvent was again removed under reduced pressure. The obtained product was dissolved in 100 ml of pure water, and an aqueous solution containing 35.1 g (0.16 mol) of potassium bis(fluorosulfonyl)imide was added as the anionic starting material. The mixture was stirred at room temperature for 5 hours. 100 ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with pure water. Next, the ethyl acetate was removed by distillation under reduced pressure to obtain ionic compound I-08. Ionic compound I-08 is represented by the following formula. [ka]

[0112] (Ionic compound I-09) In a round-bottom flask fitted with a Liebig condenser, a stirring bar, 15.5 g (68.6 mmol) of 4,5-dibromoimidazole (Sigma-Aldrich), 15.2 g (0.11 mol) of 1-bromobutane (Tokyo Chemical Industries), 27.8 g (0.2 mol) of potassium carbonate (Kanto Chemical Co., Ltd.), and 100 ml of acetone were added, and the mixture was heated under reflux at 65°C overnight. After the reaction, the reaction mixture was filtered, and the solvent from the filtrate was removed under reduced pressure. The compound was then analyzed by silica gel column chromatography (ethyl acetate). Subsequently, the obtained compound was dissolved in 50 ml of dichloromethane, and 17.1 g (0.11 mmol) of iodoethane (Tokyo Chemical Industries) was added. The mixture was heated under reflux at 40°C for 18 hours. After the reaction, the solvent was removed under reduced pressure, and after washing with diethyl ether, 4,5-dibromoethylbutylimidazolium iodide was obtained as a white powder. Next, this compound was dissolved in 300 ml of distilled THF under a nitrogen atmosphere and cooled to -78°C in a dry ice / methanol bath. Then, 80 ml of n-butyllithium / hexane 2.6 M solution (manufactured by Kanto Chemical Co., Ltd.) was slowly added dropwise, and the mixture was stirred for 30 minutes. Next, a solution of 52.3 g (0.22 mmol) of 2-bromoethoxy-tert-butyldimethylsilane (Sigma-Aldrich) dissolved in 100 ml of THF was slowly added dropwise. After reacting at -78°C for 3 hours and overnight at room temperature, hydrochloric acid was added to the reaction solution and the mixture was stirred at room temperature for 1 hour to desilylate it. After removing the solvent under reduced pressure, the mixture was separated with ethyl acetate / water, and the solvent was again removed under reduced pressure to obtain a white powder. This white powder was dissolved in 50 ml of dichloromethane, and then an aqueous solution of 20.6 g (0.07 mol) of bis(trifluoromethanesulfonyl)imide lithium, the anion starting material, was added and the mixture was stirred at room temperature for 8 hours. The resulting solution was separated to obtain an organic layer. This organic layer was washed three times with pure water. Next, the dichloromethane was removed under reduced pressure to obtain ionic compound I-09. Ionic compound I-09 is a compound represented by the following formula. [ka]

[0113] (Ionic compound I-10) Under a nitrogen atmosphere, 15.0 g (0.13 mol) of imidazole-2-ethanol (Sigma-Aldrich) and sodium hydride (60% by mass, dispersed in liquid paraffin) were used. 9.2 g of (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved in 70 ml of THF. 42.1 g (0.28 mol) of 2-bromoethanol was added dropwise over 30 minutes at room temperature, and the mixture was heated under reflux at 85°C for 12 hours. Subsequently, 100 ml of water was added to the reaction solution, and the solvent was removed under reduced pressure. 200 ml of ethanol was added to the residue, and the mixture was stirred at room temperature. Insoluble matter was removed by Celite filtration, and the solvent was again removed under reduced pressure. The obtained product was dissolved in 200 ml of pure water, and an aqueous solution containing 48.3 g (0.17 mol) of bis(trifluoromethanesulfonyl)imide lithium, the anion starting material, was added. The mixture was stirred at room temperature for 1 hour. 200 ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 120 ml of pure water. Next, the solvent was removed under reduced pressure to obtain ionic compound I-10. Ionic compound I-10 is a compound represented by the following formula. [ka]

[0114] (Ionic compound I-11) 40.0 g (0.25 mol) of 2-hydroxyethylpyridine (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved in 20 ml of acetonitrile, and 41.8 g (0.38 mol) of 3-chloro-1,2-propanediol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), dissolved in 10 ml of acetonitrile at room temperature, was added. The mixture was then heated under reflux at 90°C for 72 hours. Subsequently, the solvent was removed by distillation under reduced pressure, and the resulting reaction product was washed three times with diethyl ether. The obtained product was dissolved in 200 ml of pure water, and an aqueous solution containing 79.6 g (0.28 mol) of bis(trifluoromethanesulfonyl)imide lithium, the anionic starting material, was added, and the mixture was stirred at room temperature for 5 hours. 200 ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with pure water. Next, the solvent was removed under reduced pressure to obtain ionic compound I-11. Ionic compound I-11 is a compound represented by the following formula. [ka]

[0115] (Ionic compound I-12) 5-Methylpyrazine-2-methanol (Sigma-Aldrich) 15.0g 0.12 mol of sodium hydride (60% by mass, dispersed in liquid paraffin, manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved in 100 ml of THF. To this, 18.9 g (0.13 mol) of iodomethane (manufactured by Tokyo Chemical Industry Co., Ltd.), dissolved in 90 ml of THF, was added dropwise over 30 minutes at room temperature, and the mixture was heated under reflux at 85°C for 12 hours. Next, 100 ml of water was added to the reaction solution, and the solvent was removed under reduced pressure. 200 ml of ethanol was added to the residue, and the mixture was stirred at room temperature. Insoluble matter was removed by Celite filtration, and the solvent was again removed under reduced pressure. The obtained product was dissolved in 100 ml of pure water, and an aqueous solution containing 37.3 g (0.13 mol) of bis(trifluoromethanesulfonyl)imide lithium, the anionic starting material, was added, and the mixture was stirred at room temperature for 1 hour. 200 ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 120 ml of pure water. Next, the solvent was removed under reduced pressure to obtain ionic compound I-12. Ionic compound I-12 is represented by the following formula. [ka]

[0116] (Ionic compound I-13) In a round-bottom flask, 50 ml of purified water and 13.7 g (0.05 mol) of 2-hydroxyethyltriethylammonium iodide (manufactured by Tokyo Chemical Industry Co., Ltd.) were added and stirred for 1 hour. Next, 15.8 g (0.055 mol) of lithium bis(trifluoromethanesulfonyl)imide (trade name: EF-N115, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), dissolved in 80 ml of purified water, was added dropwise over 30 minutes as an anion exchange reagent, and the mixture was stirred at 30°C for 3 hours. The resulting reaction solution was extracted twice using 100 g of ethyl acetate. Subsequently, the separated ethyl acetate layer was washed three times with 60 g of purified water. Next, the ethyl acetate was removed under reduced pressure to obtain ionic compound I-13, whose anion is the bis(trifluoromethanesulfonyl)imide anion. Ionic compound I-13 is represented by the following formula. [ka]

[0117] (Ionic compound I-14) In a round-bottom flask, 50 ml of purified water and 17.0 g (0.10 mol) of bis(2-hydroxyethyl)dimethylammonium chloride (manufactured by Tokyo Chemical Industry Co., Ltd.) were added and stirred for 1 hour. Next, 20.6 g (0.11 mol) of lithium bis(fluorosulfonyl)imide (manufactured by Tokyo Chemical Industry Co., Ltd.), dissolved in 60 ml of purified water, was added dropwise over 30 minutes as an anion exchange reagent, and the mixture was stirred at 30°C for 3 hours. Subsequently, the separated ethyl acetate layer was washed three times with 60 g of purified water. Next, the ethyl acetate was removed under reduced pressure, and the anion was bis(fluoro) We obtained ionic compound I-14, which is a sulfonyl)imide anion. Ionic compound I-14 is represented by the following formula. [ka]

[0118] (Ionic compound I-15) 15.0 g (0.07 mol) of N,N'-bis-(2-hydroxyethyl)-2,5-dimethylpiperazine (Sigma-Aldrich) and 9.2 g of sodium hydride (60% by mass, dispersed in liquid paraffin, Tokyo Chemical Industry Co., Ltd.) were dissolved in 100 ml of THF. To this, 11.6 g (0.08 mol) of iodomethane dissolved in 90 ml of THF was added dropwise over 30 minutes at room temperature, and the mixture was heated under reflux at 85°C for 12 hours. Next, 100 ml of water was added to the reaction solution, and the solvent was removed under reduced pressure. 200 ml of ethanol was added to the residue, and the mixture was stirred at room temperature. Insoluble matter was removed by Celite filtration, and the solvent was again removed under reduced pressure. The obtained product was dissolved in 100 ml of pure water, and an aqueous solution containing 23.0 g (0.08 mol) of bis(trifluoromethanesulfonyl)imide lithium, the anionic starting material, was added, and the mixture was stirred at room temperature for 1 hour. 200 ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 120 ml of pure water. Next, the solvent was removed under reduced pressure to obtain ionic compound I-15. Ionic compound I-15 is a compound represented by the following formula. [ka]

[0119] (Ionic compound I-16) 12.9 g (0.10 mol) of 2-(2-hydroxyethyl)-1-methylpyrrolidine (manufactured by Tokyo Chemical Industry Co., Ltd.) and 8.1 g of sodium hydride (60% by mass, dispersed in liquid paraffin, manufactured by Tokyo Chemical Industry Co., Ltd.) were dissolved in 90 ml of THF. Next, the reaction system was placed under a nitrogen atmosphere and ice-cooled. To this, 16.8 g (0.11 mol) of bromoethanol dissolved in 100 ml of THF was added dropwise over 30 minutes, then the temperature was raised to room temperature, and the mixture was stirred for 1 hour. The reaction solution was heated and refluxed at 85°C for 15 hours. Next, 100 ml of water was added to the reaction solution, and the solvent was distilled off under reduced pressure. 80 ml of ethanol was added to the residue, the mixture was stirred at room temperature, insoluble matter was removed by Celite filtration, and then the solvent was distilled off again under reduced pressure. The obtained product was dissolved in 160 ml of pure water, an aqueous solution in which 31.6 g (0.11 mol) of lithium bis(trifluoromethanesulfonyl)imide was dissolved as an anion raw material was added, and the mixture was stirred at room temperature for 1 hour. 70 ml of chloroform was added to the reaction solution, and washing operations were performed 3 times using 60 ml of a 5% by mass aqueous sodium carbonate solution. Next, chloroform was distilled off under reduced pressure to obtain ionic compound I-16 . Ionic compound I-16 is a compound represented by the following formula. [Chemical Formula]

[0120] [Example 1] (Preparation of Polymer Electrolyte) As electrolyte materials, the following materials were stirred and mixed to obtain an electrolyte solution. 81.1 parts by mass of Polyol A-1 75.2 parts by mass of Isocyanate-terminated Prepolymer B-1 2.7 parts by mass of Ionic Compound I-1 13.6 parts by mass of Lithium Salt E-1 (lithium bis(trifluoromethanesulfonyl)imide (manufactured by Tokyo Chemical Industry Co., Ltd.)) 127.5 parts by mass of Methyl Ethyl Ketone (MEK)

[0121] (Measurement of Volume Swelling Rate by MEK Immersion Method) Test specimens for volume swelling rate using the MEK immersion method were prepared as follows. A predetermined amount of the electrolyte solution obtained in Example 1 was added to an aluminum mold coated with a fluororesin on its surface, so that the film thickness reached 200 μm. Next, it was placed on a sunflower stand and dried until the viscosity increased to the point where the surface of the film no longer flowed. Then, it was placed on a horizontal stand and dried at 30°C for 10 hours. Next, the electrolyte solution was heated at 120°C for 1 hour to allow it to crosslink and harden. After curing, the electrolyte film was left at 23°C and 40%RH for 24 hours, and the film was peeled from the aluminum mold to prepare a sheet with a thickness of 200 μm. The obtained polymer electrolyte sheet was cut into 50 mm x 50 mm pieces and left at 23°C and 40%RH for 24 hours to be used as test specimens.

[0122] First, the initial weight in air (W1) and the initial weight in water (W2) were measured at 23°C and 40% humidity. Next, the test specimens, after initial weight measurement, were immersed in MEK at 23°C for 48 hours. Immediately after removing the test specimens from the MEK, the MEK surface was wiped off with a nonwoven fabric, and the specimens were placed in a pre-weighed weighing bottle. The weight after immersion in air (W3) and the weight after immersion in water (W4) were then measured. The volume swelling rate after MEK immersion was calculated using the following formula. Volume swelling rate (%) = ((W3-W4)-(W1-W2)) / (W1-W2)×100 W1: Initial weight in air W2: Initial weight in water W3: Weight after immersion in air W4: Weight after immersion in water

[0123] (Ionic conductivity measurement at room temperature (25°C)) A polymer electrolyte film according to Example 1 was obtained by applying the electrolyte solution obtained in Example 1 to a 100 μm thick aluminum plate using a bar coater and heat-treating it at 120°C for 1 hour. The film thickness after curing was 50 μm.

[0124] The resulting polymer electrolyte membrane, along with the aluminum substrate, was punched out to a diameter of 50 mm and baked at 80°C for 48 hours. The polymer electrolyte membrane was then vacuum dried. Afterward, it was placed in a glove box (temperature 25°C, dew point -70°C) purged with argon. An impedance analyzer E4990A (KEYSIGHT) was used to measure the AC impedance between the electrodes at an applied voltage of 10mV and a frequency range of 100MHz to 1Hz. The bulk resistance Rb (Ω) was determined from the real impedance intercept of the resulting Cole-Cole plot, and the ionic conductivity was calculated using the following formula. σ = L / Rb × S (σ: Ionic conductivity (S·cm) -1 ), L: sample thickness (cm), S: sample area (cm) 2 ))

[0125] (Ionic conductivity measurement at low temperature (5°C)) The obtained polymer electrolyte membrane, along with the aluminum substrate, was punched out to a diameter of 10 mm and vacuum-dried at 80°C for 48 hours. The polymer electrolyte membrane was then placed in a glove box (temperature 25°C, dew point -70°C) with argon purging and assembled into an all-solid-state battery evaluation cell (manufactured by Hosen). An evaluation cell incorporating a polymer electrolyte membrane was placed in a low-temperature environment test chamber and left at 5°C for 1 hour. Subsequently, the ionic conductivity at low temperatures was determined using the same method as described above.

[0126] <Manufacturing of secondary batteries> 1. Configuration using the polymer electrolyte of this disclosure as the bulk electrolyte. (Fabrication of the negative electrode) A 20mm x 20mm, 60μm thick lithium foil (manufactured by Honjo Metal Co., Ltd.) was laminated onto a 20mm x 30mm, 20μm thick copper foil, leaving a 10mm unlaminated edge on one side, and then compressed to create a negative electrode. The total thickness of the fabricated negative electrode was 70μm. A 5mm wide copper tab, nickel-plated on one unlaminated edge, was joined to the negative electrode.

[0127] (Fabrication of the positive electrode) To 100 parts by mass of lithium cobalt oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 7 parts by mass of Kureha KH Polymer L#1120 (manufactured by Kureha Corporation) as an active material binder and 5 parts by mass of Denka Black Li-100 (manufactured by Denka Co., Ltd.) as a conductive additive were mixed, and 40 parts by mass of N-methylpyrrolidone was added thereto, followed by mixing and stirring. Next, the obtained slurry was coated on a rolled aluminum foil of 15 mm × 25 mm with a thickness of 20 μm, leaving an uncoated end portion of 10 mm on one side, followed by drying at 100°C for 30 minutes and pressing to obtain a positive electrode. The thickness of the positive electrode was 80 μm. An aluminum tab with a width of 5 mm was joined to the uncoated end portion on one side of the positive electrode.

[0128] (Formation of Polymer Electrolyte Layer) The electrolyte solution obtained in Example 1 was applied to the entire active material-coated surface of the obtained positive electrode using a bar coater, air-dried at 23°C for 10 minutes, and then heat-cured at 120°C for 1 hour. The film thickness after curing was 60 μm.

[0129] (Fabrication of Secondary Battery Using Polymer Electrolyte as Bulk Electrolyte) The positive electrode coated with the polymer electrolyte was vacuum-dried at 80°C for 48 hours. Thereafter, the polymer electrolyte membrane was placed in a glove box purged with argon (temperature 25°C, dew point -70°C), and a window frame-shaped punched polyimide sheet was attached so as to cover the outer peripheral portion of the positive electrode surface to form a short circuit prevention layer. Next, lamination was performed such that the polymer electrolyte layer of the positive electrode coated with the polymer electrolyte and the lithium layer of the negative electrode faced each other. The laminate was sandwiched between aluminum laminate films and vacuum-packed to obtain a secondary battery according to Example 1.

[0130] <Battery Characteristic Evaluation> (Rate Characteristic) The theoretical capacity was determined from the total mass of lithium cobalt oxide contained in the positive electrode. Using a charge-discharge device BCS-805 (manufactured by Bio-Logic Science Instruments), a charge-discharge test was performed on the fabricated secondary battery at 25°C . The theoretical capacity was determined from the total mass of lithium cobalt oxide contained in the positive electrode, and in the first cycle, Charging was performed for 2 hours using constant current charging at a charging rate of 0.05C and a cutoff value of 3.9V. A constant current discharge was performed at a discharge rate of 0.05C, with a cutoff value of 2.0V, for 1 hour. Next, the charge and discharge rates were increased by 0.05C increments, and the same charge and discharge cycles were performed. The rates at which charging and discharging could be performed without exceeding the cutoff value were defined as the rate characteristics.

[0131] (Strength evaluation at high temperatures) The prototype rechargeable batteries were subjected to impact testing using a thin-film impact tester QC-633 (manufactured by Cometech Testing Machines) at a temperature of 25°C. The impact was performed with a tip diameter of Φ38.1 mm, a load of 120 g, a height of 150 mm, and one repetition. After the impact, a short-circuit test was performed on the batteries using a tester. Five prototype batteries were made for each example, and a total of five impact tests were conducted. The number of batteries that short-circuited was counted. Next, the impact tester and secondary batteries were placed in an environmental tester set to 60°C and left for two hours. After that, the same tests were performed except for the measurement environment, and the number of batteries that short-circuited during the high-temperature test was counted.

[0132] (Examples 2-38) Polymer electrolytes and secondary batteries according to Examples 2 to 38 were prepared in the same manner as in Example 1, except that the types and mass parts of the polyol, isocyanate-terminated prepolymer, ionic compound, lithium salt, and MEK were changed as shown in Table 7. [Table 7]

[0133] 2. Configuration using the polymer electrolyte of this disclosure as a binder for the positive electrode active material. [Example 39] (Fabrication of the negative electrode) A 20mm x 20mm, 60μm thick lithium foil (manufactured by Honjo Metal Co., Ltd.) was laminated onto a 20mm x 30mm, 20μm thick copper foil, leaving a 10mm unlaminated edge on one side, and then compressed to create a negative electrode. The total thickness of the fabricated negative electrode was 70μm. A 5mm wide copper tab, nickel-plated on one unlaminated edge, was joined to the negative electrode.

[0134] (solid electrolyte) A LICGC (manufactured by Ohara) 20mm x 20mm, 0.18mm thick sheet was used.

[0135] (Fabrication of the positive electrode) 100 parts by mass of lithium cobalt oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was mixed with 18 parts by mass of the electrolyte solution from Example 1 (50% solids) as an active material binder and 5 parts by mass of Denka Black Li-100 (manufactured by Denka Co., Ltd.) as a conductive additive. 40 parts by mass of N-methylpyrrolidone were added and the mixture was stirred. The resulting slurry was then coated onto a 15 mm x 25 mm, 20 μm thick rolled aluminum foil, leaving a 10 mm uncoated edge on one side. The foil was heated at 120°C for one hour to cure. After curing, the foil was pressed to obtain a positive electrode with a thickness of 80 μm. A 5 mm wide aluminum tab was joined to the uncoated edge on one side of the positive electrode.

[0136] (Fabrication of secondary batteries using polymer electrolytes as binders for positive electrode active materials) A positive electrode with a polymer electrolyte as the active material binder was vacuum-dried at 80°C for 48 hours. The polymer electrolyte membrane was then placed in a glove box (temperature 25°C, dew point -70°C) with argon purging, and the positive electrode / solid electrolyte / negative electrode were stacked in that order. The stack was sandwiched between aluminum laminate films and vacuum-packed to obtain a secondary battery using the polymer electrolyte of the present disclosure as the binder for the positive electrode active material according to Example 38.

[0137] [Examples 40-43] Secondary batteries according to Examples 40-43 were prepared in the same manner as in Example 39, except that the electrolyte solution was changed as shown in Table 8. [Table 8]

[0138] 3. Configuration using the polymer electrolyte of this disclosure as a bulk electrolyte, a binder for the positive electrode active material, and a binder for the negative electrode active material. [Example 44] (Fabrication of the negative electrode) 100 parts by mass of graphite powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was mixed with 20 parts by mass of the electrolyte solution from Example 1 (50% solids) as an active material binder and 5 parts by mass of Denka Black Li-100 (manufactured by Denka Co., Ltd.) as a conductive additive. 80 parts by mass of N-methylpyrrolidone was added and the mixture was stirred. The resulting slurry was then coated onto a 20 mm x 30 mm, 20 μm thick copper foil, leaving a 10 mm uncoated edge on one side. The foil was heated at 120°C for one hour to cure. After curing, it was pressed to obtain a negative electrode with a thickness of 80 μm. Both ends were provided with uncoated negative electrode active material sections on both sides, and a 5 mm wide nickel-plated copper current collector tab was joined to one of the uncoated negative electrode active material sections.

[0139] (Fabrication of the positive electrode) Lithium cobalt oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 100 parts by mass, active material binder As a slurry, 18 parts by mass of the electrolyte solution (50% solids) from Example 1 and 5 parts by mass of Denka Black Li-100 (manufactured by Denka Co., Ltd.) as a conductive additive were mixed, and 40 parts by mass of N-methylpyrrolidone were added and mixed and stirred. Next, the obtained slurry was coated onto a 20 μm thick rolled aluminum foil and heated at 120°C for one hour to cure. After curing, it was pressed to obtain a positive electrode with a thickness of 80 μm. Both ends were provided with areas where the positive electrode active material was not coated on either side, and a 5 mm wide aluminum current collector tab was joined to one of the areas where the positive electrode active material was not coated.

[0140] (Formation of polymer electrolyte layer) The electrolyte solution from Example 1 was applied to the obtained positive electrode using a bar coater, and cured by heating at 120°C for one hour. The film thickness after curing was 60 μm.

[0141] (Fabrication of secondary batteries using polymer electrolytes as bulk electrolyte, binder for positive electrode active material, and binder for negative electrode active material) The positive electrode and negative electrode, coated with polymer electrolyte, were vacuum-dried at 80°C for 48 hours. The polymer electrolyte film was then placed in a glove box (temperature 25°C, dew point -70°C) purged with argon, and a polyimide sheet, punched into a window frame shape, was attached to cover the outer periphery of the positive electrode surface to form a short-circuit prevention layer. Next, the polymer electrolyte layer of the positive electrode and the active material layer of the negative electrode were laminated so that they corresponded to each other. The laminate was sandwiched between aluminum laminate films and vacuum-packed to obtain a secondary battery using the polymer electrolyte of the present disclosure as the bulk electrolyte, binder for the positive electrode active material, and binder for the negative electrode active material, as described in Example 44.

[0142] [Examples 45-48] Secondary batteries according to Examples 45-48 were prepared in the same manner as in Example 44, except that the electrolyte solution was changed as shown in Table 9. [Table 9]

[0143] (Comparative Example 1) The following materials were mixed together by stirring to form the electrolyte. Polyol A-1 92.7 parts by mass Isocyanate-terminated prepolymer B-1: 62.4 parts by mass Lithium salt E-1 13.6 parts by mass Methyl ethyl ketone 131.3 parts by mass The electrolyte membrane and secondary battery according to Comparative Example 1 were fabricated in the same manner as in Example 1.

[0144] (Comparative Examples 2-6) Polymer electrolytes and secondary batteries according to Comparative Examples 2 to 6 were prepared in the same manner as in Comparative Example 1, except that the types and mass parts of the polyol, isocyanate-terminated prepolymer, ionic compound, lithium salt, and MEK were changed as shown in Table 10.

[0145] (Comparative Examples 7-9) Secondary batteries according to Comparative Examples 7-9 were prepared in the same manner as in Example 38, except that the electrolyte solution was changed as shown in Table 10.

[0146] (Comparative Examples 10-12) Secondary batteries according to Comparative Examples 10 to 12 were prepared in the same manner as in Example 44, except that the electrolyte solution was changed as shown in Table 10. [Table 10]

[0147] The polymer electrolytes and secondary batteries obtained in Examples 2-48 and Comparative Examples 1-12 were evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 11-14. [Table 11] [Table 12] [Table 13] [Table 14]

[0148] The polymer electrolytes of Examples 1 to 38 exhibit high ionic conductivity at both 25°C and 5°C because they have a cation structure within the polyurethane molecule. Furthermore, secondary batteries using the polymer electrolyte as a bulk electrolyte also exhibit high rate characteristics and high impact resistance at high temperatures. Furthermore, the average number of moles added of the ethylene oxide structure represented by formula (7) in polyurethane is m. 1 And the average number of added moles n of the propylene oxide structure shown in equation (8) 1 toga, n 1 ≤m 1 ≤9n 1 Examples 1 to 31 that satisfied the criteria showed higher ionic conductivity and also exhibited good rate characteristics for secondary batteries. On the other hand, the polymer electrolytes in Comparative Examples 1 to 5, which lacked a cation structure within the polyurethane molecule, exhibited low ionic conductivity and poor rate characteristics in secondary batteries. In Comparative Example 6, where the polyurethane dissolved during volume swelling measurement, ionic conductivity was high, but the impact resistance of the secondary battery at high temperatures decreased. This is thought to be because the polyurethane in Comparative Example 6 lacked a three-dimensional crosslinked structure. In Examples 39-48, where the usage site of the polymer electrolyte in the secondary battery was changed, the polyurethane molecules with a three-dimensional crosslinked structure had a cationic structure, resulting in high rate characteristics and high impact resistance at high temperatures in the secondary battery. On the other hand, Comparative Examples 7-8 and 10-11, which did not have a cationic structure in the polymer structure, showed low ionic conductivity and poor rate characteristics in the secondary battery, even when the usage site in the secondary battery was changed. Comparative Examples 9 and 12, in which the polyurethane did not have a three-dimensional crosslinked structure, showed a significant decrease in the impact resistance of the secondary battery at high temperatures.

[0149] This disclosure relates to the following configuration. [Configuration 1] A polymer electrolyte, The polymer electrolyte contains polyurethane, a lithium salt, and an anion. The polyurethane is a polymer electrolyte having a three-dimensional crosslinked structure and a cation structure within the molecule. [Configuration 2] The polymer electrolyte according to configuration 1, wherein the volume swelling rate of the polymer electrolyte by methyl ethyl ketone immersion is 30.0 to 100.0%. [Configuration 3] The polymer electrolyte according to configuration 1 or 2, wherein the cation structure comprises at least one selected from the group consisting of a cationic nitrogen-containing heterocyclic structure and an ammonium cation having a linear or branched structure. [Structure 4] The polymer electrolyte according to any of configurations 1 to 3, wherein the cation structure is a cationic nitrogen-containing heterocyclic structure. [Composition 5] The polymer electrolyte according to configuration 3 or 4, wherein the cationic nitrogen-containing heterocyclic structure comprises at least one selected from the group consisting of imidazolium cation, pyridinium cation, pyrazinium cation, pyrrolidinium cation, and piperazinium cation. [Composition 6] The polymer electrolyte according to configuration 3, wherein the linear or branched ammonium cation is a quaternary ammonium cation. [Composition 7] The polymer electrolyte according to any one of configurations 1 to 6, wherein the cation structure includes at least one structure selected from the group consisting of structures represented by the following formulas (1) to (6). TIFF0007933647000042.tif35170 (in formula (1), d 1 represents an integer from 0 to 3, R 1 and R 2 This represents a hydrocarbon group that forms a five-membered ring nitrogen-containing aromatic heterocyclic structure together with a nitrogen atom. Z 1 ~Z 2 Each of these independently represents the structure shown in the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 3 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 1 , Z 2 , and d 1 When is 1 or more, at least one Z 3 From a group consisting of At least one of the selected structures is represented by the following formula (X). TIFF0007933647000043.tif33170 (in formula (2), d 2 This represents an integer from 0 to 5, R 3 This represents a hydrocarbon group that forms a nitrogen-containing aromatic heterocyclic structure together with a nitrogen atom. Z 4This represents the structure shown by formula (X) below, a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 5 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 4 , and d 2 When is 1 or more, at least one Z 5 At least one selected from the group consisting of the following is a structure represented by the following formula (X). TIFF0007933647000044.tif36170 (in formula (3), d 3 represents an integer from 0 to 4, R 4 and R 5 This represents a hydrocarbon group that forms a six-membered ring nitrogen-containing aromatic heterocyclic structure together with a nitrogen atom. Z 6 This represents the structure shown by formula (X) below, a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 7 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 6 , and d 3 When is 1 or more, at least one Z 7 At least one selected from the group consisting of the following is a structure represented by the following formula (X). TIFF0007933647000045.tif35170(In formula (4), R 7 represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, Z 8 ~Z 10 Each of these independently represents the structure shown in the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms with a hydroxyl group, and Z 8 ~Z 10 At least one of the groups consisting of the following is a structure represented by the following formula (X). TIFF0007933647000046.tif32170 (in formula (5), d 4 represents an integer from 0 to 4, R 8 and R 9 This represents a hydrocarbon group that forms a nitrogen-containing aliphatic heterocyclic structure together with a nitrogen atom. Z 11 ~Z 13 Each of these independently represents the structure shown in the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 14 Each of these independently represents the structure shown in the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 11 ~Z 13 , and d 4 When is 1 or more, at least one Z 14 At least one selected from the group consisting of , is a structure represented by the following formula (X). TIFF0007933647000047.tif32170 (in formula (6), d 5 represents an integer from 0 to 4, R 9 This represents a hydrocarbon group that forms a nitrogen-containing aliphatic heterocyclic structure together with a nitrogen atom. Z 15 ~Z 16 Each of these independently represents the structure, hydrogen atom, hydroxyl group, or structure shown by the following formula (X). This represents a hydrocarbon group having 1 to 4 carbon atoms or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 17 Each of these independently represents the structure, hydroxyl group, or C1-C4 hydrocarbon group or C1-C4 hydrocarbon group having a hydroxyl group shown in the following formula (X): Z 15 , Z 16 , and d 5 When is 1 or more, at least one Z 17 At least one selected from the group consisting of , is a structure represented by the following formula (X). TIFF0007933647000048.tif18170(In formula (X), R 10 The symbol "*" represents a linear or branched divalent hydrocarbon group, the symbol "*" represents a bond with a nitrogen atom in formulas (1) to (6), or a bond with a carbon atom in the nitrogen-containing heterocyclic structure in formulas (1) to (3) and formulas (5) to (6), and the symbol "**" represents a bond with a carbon atom in the polymer chain constituting the polyurethane having the aforementioned cationic structure. [Structure 8] The polymer electrolyte according to any one of configurations 1 to 9, wherein the polyurethane has at least an ethylene oxide structure represented by the following formula (7) between a first urethane bond and a second urethane bond adjacent to each other. TIFF0007933647000049.tif13170[Configuration 9] The polymer electrolyte according to configuration 8, further comprising a propylene oxide structure represented by the following formula (8) between the first urethane bond and the second urethane bond. TIFF0007933647000050.tif22170[Configuration 10] The average number of moles added to the ethylene oxide structure is m. 1 , and the average number of added moles n of the propylene oxide structure 1 Each of these is an independent natural number greater than or equal to 1, and n 1 ≤m 1 ≤9n 1 The polymer electrolyte described in configuration 9. [Composition 11] The polymer electrolyte according to any of the configurations 1 to 10, wherein the polymer electrolyte is a dry polymer electrolyte. [Composition 12] At least one polyol, At least one isocyanate compound, Anions and, An ionic compound having a functional group that can react with an isocyanate group and containing a cationic structure, Lithium salts and It is a cured product of a mixture containing, The mixture is The at least one polyol is a polyol having at least three hydroxyl groups, The at least one isocyanate compound is an isocyanate compound having at least three isocyanate groups, A polymer electrolyte comprising at least one selected from the group consisting of the following. [Composition 13] The mixture comprises, as at least one polyol, a polyol with a molecular weight of 3000 to 5000 having an ethylene oxide structure represented by the following formula (7) and a propylene oxide structure represented by the following formula (8), and The polymer electrolyte according to claim 12, wherein the at least one isocyanate compound comprises a urethane prepolymer. TIFF0007933647000051.tif13170TIFF0007933647000052.tif22170[Composition 14] An electrode active material binder containing a polymer electrolyte described in any of the configurations 1 to 13. [Composition 15] A secondary battery comprising a positive electrode, a negative electrode, and a bulk electrolyte disposed between the positive electrode and the negative electrode, wherein at least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte comprises a polymer electrolyte as described in any of configurations 1 to 13. [Composition 16] The secondary battery according to configuration 15, wherein the positive electrode comprises a positive electrode active material and a binder for the positive electrode active material, and the binder comprises the polymer electrolyte. [Composition 17] The secondary battery according to configuration 15 or 16, wherein the negative electrode comprises a negative electrode active material and a binder for the negative electrode active material, and the binder comprises the polymer electrolyte. [Composition 18] A secondary battery according to any configuration 15 to 18, wherein the bulk electrolyte includes the polymer electrolyte. [Composition 19] The secondary battery according to any of the configurations 15 to 18, wherein the secondary battery is an all-solid-state secondary battery. [Explanation of Symbols]

[0150] 1: Secondary battery, 2: Positive electrode current collector, 3: Positive electrode active material, 4: Binder for positive electrode active material, 5: Conductive additive, 6: Positive electrode, 7: Bulk electrolyte, 8: Negative electrode active material, 9: Negative electrode current collector, 10: Negative electrode, 11: Binder for negative electrode active material

Claims

1. A polymer electrolyte, The polymer electrolyte contains polyurethane, a lithium salt, and an anion. A polymer electrolyte characterized in that the polyurethane has a three-dimensional crosslinked structure and has a cation structure bonded to the polymer chain constituting the polyurethane within the molecule.

2. The polymer electrolyte according to claim 1, wherein the volume swelling rate of the polymer electrolyte by methyl ethyl ketone immersion is 30.0 to 100.0%.

3. The polymer electrolyte according to claim 1, wherein the cation structure comprises at least one selected from the group consisting of a cationic nitrogen-containing heterocyclic structure and an ammonium cation having a linear or branched structure.

4. The polymer electrolyte according to claim 3, wherein the cation structure is a cationic nitrogen-containing heterocyclic structure.

5. The polymer electrolyte according to claim 4, wherein the cationic nitrogen-containing heterocyclic structure comprises at least one selected from the group consisting of imidazolium cation, pyridinium cation, pyrazinium cation, pyrrolidinium cation, and piperazinium cation.

6. The polymer electrolyte according to claim 3, wherein the linear or branched ammonium cation is a quaternary ammonium cation.

7. The polymer electrolyte according to claim 1, wherein the cation structure includes at least one structure selected from the group consisting of structures represented by the following formulas (1) to (6). (In formula (1), d 1 represents an integer from 0 to 3, R 1 and R 2 This represents a hydrocarbon group that forms a five-membered ring nitrogen-containing aromatic heterocyclic structure together with a nitrogen atom. Z 1 ~Z 2 Each of these independently represents the structure shown in the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 3 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 1 , Z 2 , and d 1 is 1 or more, at least one Z 3 selected from the group consisting of has a structure represented by the following formula (X).) (In formula (2), d 2 represents an integer from 0 to 5, R 3 This represents a hydrocarbon group that forms a nitrogen-containing aromatic heterocyclic structure together with a nitrogen atom. Z 4 This represents the structure shown by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 5 This represents the structure shown by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 4 , and d 2 When there is 1 or more, at least one Z 5 At least one selected from the group consisting of the following is a structure represented by the following formula (X). (In formula (3), d 3 represents an integer from 0 to 4, R 4 and R 5 This represents a hydrocarbon group that forms a six-membered ring nitrogen-containing aromatic heterocyclic structure together with a nitrogen atom. Z 6 This represents the structure shown by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 7 This refers to a structure represented by the following formula (X), a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydroxyl group. This represents a hydrocarbon group having 1 to 4 carbon atoms, Z 6 , and d 3 When there is 1 or more, at least one Z 7 At least one selected from the group consisting of the following is a structure represented by the following formula (X). (In formula (4), R 7 represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, Z 8 ~Z 10 Each of these independently represents the structure shown in the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms with a hydroxyl group, and Z 8 ~Z 10 At least one of the groups consisting of the following is a structure represented by the following formula (X). (In formula (5), d 4 represents an integer from 0 to 4, R 8 and R 9 This represents a hydrocarbon group that forms a nitrogen-containing aliphatic heterocyclic structure together with a nitrogen atom. Z 11 ~Z 13 Each of these independently represents the structure shown in the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 4 carbon atoms that has a hydroxyl group. Z 14 Each of these independently represents a structure, a hydroxyl group, a C1-C4 hydrocarbon group, or a C1-C4 hydrocarbon group having a hydroxyl group, Z 11 ~Z 13 , and d 4 When there is 1 or more, at least one Z 14 At least one selected from the group consisting of , is a structure represented by the following formula (X). (In formula (6), d 5 represents an integer from 0 to 4, R 9 This represents a hydrocarbon group that forms a nitrogen-containing aliphatic heterocyclic structure together with a nitrogen atom. Z 15 ~Z 16 Each of these independently represents the structure shown in the following formula (X), a hydrogen atom, a hydroxyl group, or a hydrocarbon group having 1 to 4 carbon atoms or a hydrocarbon group having 1 to 4 carbon atoms with a hydroxyl group. Z 17 Each of these independently represents the structure, hydroxyl group, or C1-C4 hydrocarbon group or C1-C4 hydrocarbon group having a hydroxyl group shown in the following formula (X), Z 15 Z 16 , and d 5 When there is 1 or more, at least one Z 17 At least one selected from the group consisting of , is a structure represented by the following formula (X). (In formula (X), R 10 The symbol "*" represents a divalent hydrocarbon group having a straight or branched chain, the symbol "*" represents a bond with a nitrogen atom in formulas (1) to (6), or a bond with a carbon atom in the nitrogen-containing heterocyclic structure in formulas (1) to (3) and formulas (5) to (6), and the symbol "**" represents a bond with a carbon atom in the polymer chain constituting the polyurethane having the aforementioned cationic structure.

8. The polymer electrolyte according to claim 1, wherein the polyurethane has at least an ethylene oxide structure represented by the following formula (7) between a first urethane bond and a second urethane bond adjacent to each other.

9. The polymer electrolyte according to claim 8, further comprising a propylene oxide structure represented by the following formula (8) between the first urethane bond and the second urethane bond.

10. The average number of moles added to the ethylene oxide structure is m. 1 , and the average number of moles added to the propylene oxide structure n 1 Each of these is an independent natural number greater than or equal to 1, and n 1 ≤m 1 ≤9n 1 The polymer electrolyte according to claim 9.

11. The polymer electrolyte according to claim 1, wherein the polymer electrolyte is a dry polymer electrolyte.

12. At least one polyol, At least one isocyanate compound, Anions and, An ionic compound having a functional group that can react with an isocyanate group and containing a cationic structure, Lithium salts and It is a cured product of a mixture containing, The mixture is The at least one polyol is a polyol having at least three hydroxyl groups, The at least one isocyanate compound is an isocyanate compound having at least three isocyanate groups, A polymer electrolyte characterized by comprising at least one selected from the group consisting of the following.

13. The mixture comprises, as at least one polyol, a polyol with a molecular weight of 3000 to 5000 having an ethylene oxide structure represented by the following formula (7) and a propylene oxide structure represented by the following formula (8), and The polymer electrolyte according to claim 12, wherein the at least one isocyanate compound comprises a urethane prepolymer.

14. An electrode active material binder characterized by containing a polymer electrolyte according to any one of claims 1 to 13.

15. A secondary battery comprising a positive electrode, a negative electrode, and a bulk electrolyte disposed between the positive electrode and the negative electrode, wherein at least one selected from the group consisting of the positive electrode, the negative electrode, and the bulk electrolyte contains a polymer electrolyte according to any one of claims 1 to 13.

16. The secondary battery according to claim 15, wherein the positive electrode comprises a positive electrode active material and a binder for the positive electrode active material, and the binder comprises the polymer electrolyte.

17. The secondary battery according to claim 15, wherein the negative electrode comprises a negative electrode active material and a binder for the negative electrode active material, and the binder comprises the polymer electrolyte.

18. The secondary battery according to claim 15, wherein the bulk electrolyte comprises the polymer electrolyte.

19. The secondary battery according to claim 15, wherein the secondary battery is an all-solid-state secondary battery.

Citation Information

Patent Citations

  • Polymer electrolyte composition, negative electrode for lithium metal secondary battery, electrolyte for lithium ion secondary battery, and metal secondary battery and lithium ion secondary battery using them

    JP2016069388A

  • Solid electrolyte composition, solid electrolyte-containing sheet, electrode sheet for all-solid-state secondary batteries, all-solid-state secondary battery, method for producing solid electrolyte-containing sheet, method for producing electrode sheet for all-solid-state secondary batteries, and method for manufacturing all-solid-state secondary battery

    WO2017209233A1

  • Solid electrolyte composition, solid-electrolyte-containing sheet and all-solid-state secondary battery, production method for solid-electrolyte-containing sheet and all-solid-state secondary battery, segmented polymer, and non-aqueous-solvent dispersion of polymer and segmented polymer

    WO2018020827A1

  • Solid electrolyte composition, solid electrolyte-containing sheet, all-solid-state secondary battery, and production method for solid electrolyte-containing sheet and all-solid-state secondary battery

    WO2019017311A1